Electrophotographic member, process cartridge and electrophotographic image formation device
By adopting a multiphase structural design with conductive surfaces, elastic layers and surface layers in the electro-optical image forming members, the excessive discharge caused by dirt accumulation under high speed and clean member configuration is solved, and a long-term high-quality image formation effect is achieved.
Patent Information
- Application Number
- JP2023166398
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-27
- Publication Date
- 2025-04-09
AI Technical Summary
During the electro-optical image formation process under high speed and clean member configuration, the charge members of the electro-optical image forming device are prone to excessive discharge due to dirt accumulation, resulting in white spot images.
An electro-optical image forming member is employed, which includes a substrate having a conductive surface, an elastic layer covered on the conductive surface, and a surface layer in contact with the elastic layer. The surface layer contains electronic conductive agent, and the outer surface is covered with a metal film, which has a specific impedance value when the AC voltage is applied under specific environmental conditions. The elastic layer has a multiphase structure, including a conductive second rubber phase and an insulated first rubber phase, ensuring effective charge exchange between the conductive particles at different levels.
This solution effectively inhibits the accumulation of dirt on charge members, prevents excessive discharge, and ensures high-quality image formation for a long time at high speed and clean member configurations.
Smart Images

Figure 2025056886000001_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure relates to an electrophotographic member, a process cartridge, and an electrophotographic image forming apparatus that can be used in electrophotography. [Background technology]
[0002] The electrophotographic image forming apparatus has a charging member, a transfer member, and a developing member. The charging member is a member that generates a discharge between itself and an electrophotographic photoreceptor to charge the surface of the electrophotographic photoreceptor. The developing member is a member that controls the charge of the developer coated on its surface by frictional charging, gives a uniform charge distribution, and uniformly transfers the developer to the surface of the electrophotographic photoreceptor according to an applied electric field. The transfer member is a member that transfers the developer from the electrophotographic photoreceptor to a print medium such as paper or an intermediate transfer member, and at the same time generates a discharge to stabilize the developer after transfer.
[0003] In the electrophotographic image forming process, the surface of the photoreceptor is charged, and then exposed to light to draw a latent image, toner is transferred to the latent image on the surface of the photoreceptor by a developing member, and the toner is transferred to a paper medium by a transfer member. When transferring to the paper medium, toner that remains on the photoreceptor without being transferred to the paper (hereinafter also referred to as "transfer residual toner") is scraped off by a cleaning member and removed from the surface of the photoreceptor. However, if the cleaning member cannot completely scrape off the toner, the toner and external additives may adhere to the surface of the charging member as contaminants, and the contaminants may cause over-discharge, resulting in the generation of white spotted images (hereinafter also referred to as "white spot images").
[0004] Patent Document 1 discloses a charging member that applies a uniform charge to contaminants adhering to the charging member surface and expels the contaminants from the charging member surface to the photoreceptor surface, thereby suppressing the accumulation of the contaminants on the charging member surface. The charging member has a surface layer formed on an elastic layer, and the elastic layer has a matrix-domain structure in which domains made of a second rubber and a conductive agent are dispersed in a matrix made of a first rubber. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Patent Publication No. 2021-067946 Summary of the Invention [Problem to be solved by the invention]
[0006] In recent years, electrophotographic image forming processes have become faster and have longer life spans, and in order to reduce the size of the device, electrophotographic image forming devices have been provided that do not have a cleaning member for removing residual toner remaining on the photoconductor (hereinafter also referred to as a "cleanerless configuration"). When the present inventors carried out a durability evaluation of a faster process and cleanerless configuration using the charging member of Patent Document 1, the accumulation of dirt on the charging member became noticeable even at a print count where the accumulation of dirt on the charging member was not a problem in the past, and white spots were sometimes generated due to excessive discharge caused by the dirt.
[0007] At least one aspect of the present disclosure is directed to an electrophotographic member that enables high-quality image formation for a long period of time even under severe conditions of further increasing the speed of an electrophotographic image formation process and accumulating dirt on the electrophotographic member, such as a cleaner-less configuration. At least one aspect of the present disclosure is directed to a process cartridge that contributes to high-quality electrophotographic image formation. At least one aspect of the present disclosure is directed to a process cartridge that contributes to high-quality electrophotographic image formation. The present invention is directed to an electrophotographic imaging apparatus capable of forming an image thereon. [Means for solving the problem]
[0008] According to at least one aspect of the present disclosure, there is provided an electrophotographic member comprising a substrate having an electrically conductive surface, an elastic layer on the electrically conductive surface of the substrate, and a surface layer in contact with a surface of the elastic layer opposite a surface facing the substrate, the surface layer comprising: the surface layer comprises an electronic conductive agent, A metal film is provided on the outer surface of the surface layer of the electrophotographic member, and an AC voltage having an amplitude of 1 V and a frequency of 1.0 Hz is applied between the conductive surface of the substrate and the metal film in an environment of a temperature of 23° C. and a relative humidity of 50%, and the impedance is 1.0×10 3 ~1.0×10 8 Ω, the elastic layer includes an insulating first phase including at least a cross-linked product of a first rubber, and a second phase including a cross-linked product of a second rubber different from the first rubber and conductive particles; The thickness of the elastic layer is 10 μm or more, the elastic layer has a matrix-domain structure in which domains made of the second phase are dispersed in a matrix made of the first phase in a region extending from an interface between the elastic layer and the surface layer to a depth direction of 5 μm or more into the elastic layer, A region having a thickness of 1 μm from the interface between the elastic layer and the surface layer to a position 1 μm deep into the elastic layer is defined as region A, A region having a thickness of 1 μm from the interface to a position 5 μm to 6 μm in a depth direction into the elastic layer is defined as region B, a first surface of the elastic layer in the region A is exposed, and a first observation region having a square shape with one side of 100 μm is placed at an arbitrary position on the first surface using a scanning electron microscope; the first observation region contains at least the second phase; The ratio (AR12 / AR11) of the sum AR12 of the area of the second phase in the first observation region to the area AR11 of the first observation region is greater than 0.40; and When the second surface of the elastic layer in the region B is exposed and a square second observation region with a side length of 100 μm is placed at an arbitrary position on the second surface using a scanning electron microscope, the matrix-domain structure is observed in the second observation region, and the ratio (AR22 / AR21) of the sum AR22 of the area of the second phase in the second observation region to the area AR21 of the second observation region is 0.40 or less. An electrophotographic member is provided.
[0009] According to at least one aspect of the present disclosure, there is provided a process cartridge detachably mountable to an electrophotographic image forming apparatus, the process cartridge including the electrophotographic member described above.
[0010] According to at least one aspect of the present disclosure, there is provided an electrophotographic image forming apparatus, comprising: An electrophotographic imaging apparatus is provided comprising the above electrophotographic member. Effect of the Invention
[0011] According to at least one aspect of the present disclosure, an electrophotographic member capable of forming high-quality images for a long period of time even under severe conditions of further increasing the speed of an electrophotographic image forming process and accumulating dirt on the electrophotographic member, such as a cleanerless configuration, can be provided. Also, according to at least one aspect of the present disclosure, a process cartridge contributing to high-quality electrophotographic image formation can be provided. Furthermore, according to at least one aspect of the present disclosure, an electrophotographic image forming apparatus capable of forming high-quality electrophotographic images can be provided. [Brief description of the drawings]
[0012] [Figure 1] Cross-sectional view of a conductive roller [Diagram 2] Schematic diagram of a crosshead extruder [Diagram 3] Schematic cross-sectional view of a process cartridge [Figure 4] Schematic diagram of an electrophotographic image forming apparatus DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] In the present disclosure, the description of "XX or more and YY or less" or "XX to YY" expressing a numerical range means a numerical range including the lower and upper limits, which are the endpoints, unless otherwise specified. When a numerical range is described in stages, the upper and lower limits of each numerical range can be arbitrarily combined. In addition, in the present disclosure, a description such as "at least one selected from the group consisting of XX, YY, and ZZ" means any of XX, YY, ZZ, a combination of XX and YY, a combination of XX and ZZ, a combination of YY and ZZ, or a combination of XX, YY, and ZZ.
[0014] The present inventors have investigated why the charging member according to Patent Document 1 further increases the process speed and, in the case of a cleaner-less configuration, causes significant accumulation of contaminating substances such as toner and external additives on the charging member at a print count that previously did not pose a problem in terms of images, resulting in the appearance of white spots on electrophotographic images.
[0015] First, the process by which contaminants such as toner and external additives adhere to the surface of a charging member will be described. Toner and external additives are required to have a certain charge so that they can be properly transferred to a photoconductor in a development process, and therefore often have insulating properties. For this reason, toner and external additives as contaminants also have insulating properties. In a developing container, toner and external additives are charged with a polarity that is significantly biased toward positive or negative. In contrast, contaminants such as toner and external additives that are not transferred to paper or an intermediate transfer body and remain on the photoconductor drum are affected by friction and the like before reaching the charging member, and thus are charged with a certain distribution of positive and negative polarities.
[0016] On the other hand, the charging member is configured to generate a discharge to the photoconductor. Specifically, a DC voltage is applied to the charging member to generate a potential difference between the charging member and the surface of the photoconductor. In this case, it is difficult to prevent contaminant components having a polarity opposite to that of the charging bias from adhering to the charging member due to electrostatic attraction with respect to the potential difference between the charging member and the photoconductor, and the contaminant substances migrate from the photoconductor to the charging member.
[0017] Next, we will explain white dot images that occur due to abnormal discharge caused by contaminants. A discharge phenomenon occurs between the charging member and the photoconductor according to Paschen's law, and the surface of the photoconductor is charged with negative or positive charges depending on the applied voltage. Since discharge occurs when neutral air is ionized by an electric field, charges of the opposite polarity are also generated at the same time. That is, while the photoconductor is charged with negative or positive charges by the discharge, charges of the opposite polarity to the charges that charge the photoconductor are also drawn toward the charging member by the electric field.
[0018] When the charging member is contaminated by insulating contaminants, the charges of the opposite polarity approaching the charging member are trapped on the surface of the charging member without passing through the surface to the substrate, and the contaminants attached to the surface of the charging member are charged with the opposite polarity. Between the contaminants charged with the opposite polarity and the surrounding area of the area where the contaminants are attached, charges of the opposite polarity are present in a very short distance. This generates a very strong electric field, which causes abnormally large discharges and white spots to appear.
[0019] Next, the "ejection" phenomenon, in which the contaminant material adhering to the surface of the charging member is returned to the photoconductor, will be described. When the contaminant material adheres to the charging member, a charge of the same polarity as the applied bias is gradually imparted to the contaminant material from the outer surface, depending on whether the applied bias is negative or positive. When a sufficient charge is accumulated on the contaminant, an electrostatic force acts in the electric field formed from the surface of the charging member toward the photoconductor drum, and exceeds the adhesive force between the surface of the charging member and the contaminant, causing a "discharge" phenomenon in which the contaminant peels off from the surface of the charging member and moves to the photoconductor side. In other words, if a sufficient charge is accumulated for most of the contaminant and the discharge phenomenon occurs efficiently, the accumulation of the contaminant can be prevented.
[0020] The charging member of Patent Document 1 has a structure in which an electronic conductive agent is added to an elastic layer having a matrix-domain structure as described above. The outer peripheral surface of the domain in the matrix-domain structure has few irregularities and the domain is close to a perfect sphere, so that it is difficult to create a concentration point for the exchange of electrons between the domains. Furthermore, the presence of a conductive surface layer in which an electronic conductive agent is dispersed makes it possible to uniformly apply a charge of the same polarity as the applied bias to the contaminants.
[0021] However, in the charging member of Patent Document 1, there are cases where an area where the connection of the conductive path by the domain in the elastic layer and the conductive particles in the surface layer is weak is formed. In such a case, the charge stagnates at the interface between the elastic layer and the surface layer, and sufficient charge cannot be applied to the contaminant substance, so that the contaminant substance accumulates without being discharged. This phenomenon is remarkable in a high-speed process. In addition, in the case of a cleaner-less configuration, a lot of contaminant substances migrate to the charging member surface as transfer residual toner, etc. Therefore, it is not possible to apply a charge of the same polarity as the applied bias to all the contaminant substances, and some of the contaminant substances that cannot be discharged remain on the photoconductor, causing accumulation of the contaminant substances.
[0022] From the above, the present inventors have recognized that in order to suppress the accumulation of contaminants in a high-speed process and in a cleanerless configuration, it is necessary to more efficiently transfer charges between the domains in the elastic layer and the conductive paths of the conductive particles in the surface layer in the above configuration. Based on this recognition, the present inventors have conducted further studies and found that in an electrophotographic member including a substrate having a conductive surface, an elastic layer on the conductive surface of the substrate, and a surface layer in contact with the surface of the elastic layer opposite to the surface facing the substrate, by satisfying all of the following requirements (A) to (D), it is possible to suppress the occurrence of white dot images for a long period of time even in a system that is strict on contaminants, such as a high-speed process and a cleanerless configuration.
[0023] ·Requirements (A) A metal film is provided on the outer surface of the surface layer of an electrophotographic member, and an AC voltage having an amplitude of 1 V and a frequency of 1.0 Hz is applied between the conductive surface of the substrate and the metal film in an environment of a temperature of 23° C. and a relative humidity of 50%. The impedance is 1.0×10 3 ~1.0×10 8 It is Omega.
[0024] ·Requirements (B) The elastic layer includes an insulating first phase including at least a first rubber, and a second phase including a second rubber different from the first rubber and conductive particles, and the thickness of the elastic layer is 10 μm or more. A region having a thickness of 1 μm from the interface between the elastic layer and the surface layer to a position 1 μm deep into the elastic layer is defined as region A. When the first surface in region A is exposed and a first observation region having a square shape with one side of 100 μm is placed at an arbitrary position on the first surface using a scanning electron microscope, the first observation region includes at least a second phase including a second rubber and conductive particles. The ratio (AR12 / AR11) of the sum AR12 of the areas of the second phases in the first observation region to the area AR11 of the first observation region is greater than 0.40.
[0025] ·Requirements (C) The elastic layer has a matrix structure in which domains of the second phase are dispersed in a matrix of the first phase in a region of 5 μm or more in a depth direction from the interface between the elastic layer and the surface layer into the elastic layer. The elastic layer has a matrix-domain structure. A region having a thickness of 1 μm from the interface between the elastic layer and the surface layer to a position 5 μm to 6 μm in the depth direction into the elastic layer is designated as Region B. When the second surface in Region B is exposed and a square second observation region with a side length of 100 μm is placed on the second surface using a scanning electron microscope, the matrix-domain structure is observed in the second observation region. Furthermore, the ratio (AR22 / AR21) of the sum AR22 of the area of the second phase in the second observation region to the area AR21 of the second observation region is 0.40 or less.
[0026] ·Requirements (D) The surface layer includes an electronic conductive agent.
[0027] Each requirement is explained in detail below. <Requirements (A)> Requirement (A) represents the degree of conductivity of an electrophotographic member. An electrophotographic member exhibiting such an impedance value can suppress an excessive increase in the amount of discharge current, and as a result, can prevent the occurrence of uneven potential of charging due to abnormal discharge. In addition, it can suppress a shortage of injected charge supplied to a contaminant. The impedance is 1.0×10 4 ~1.0×10 7 It is preferably Ω. The impedance can be controlled by the volume resistivity of the domain and the amount of the domain in the matrix-domain structure.
[0028] The impedance required for requirement (A) can be measured by the following method: First, in order to eliminate the influence of contact resistance between the electrophotographic member and the measurement electrode, a low-resistance thin film is deposited on the outer surface of the surface layer of the electrophotographic member, and the thin film is used as an electrode while the conductive substrate is used as a ground electrode to measure the impedance via two terminals.
[0029] Examples of the method for forming the thin film include metal deposition, sputtering, application of a metal paste, and application of a metal tape. Among these, from the viewpoint of reducing the contact resistance with the electrophotographic member, a method for forming a metal film such as platinum or palladium as an electrode by deposition is preferred. In the present disclosure, a platinum metal film is used.
[0030] When forming a metal film on the surface of an electrophotographic member, in consideration of the ease of forming the metal film and the uniformity of the thin film, it is preferable to provide a vacuum deposition apparatus with a mechanism for holding the electrophotographic member. For electrophotographic members having a cylindrical cross section, it is preferable to use a vacuum deposition apparatus further provided with a rotation mechanism.
[0031] For electrophotographic members having a circular or other curved cross section, for example, a cylindrical electrophotographic member, it is difficult to connect the metal film as the measurement electrode to the impedance measuring device, so it is preferable to use the following method. Specifically, after forming a metal film electrode with a width of about 10 mm to 20 mm in the longitudinal direction of the electrophotographic member, a metal sheet is tightly wrapped around the electrophotographic member, and the metal sheet is connected to the measurement electrode protruding from the measuring device for measurement. This allows the measuring device to suitably obtain an electric signal from the surface layer of the electrophotographic member, and impedance measurement can be performed. The metal sheet may be any metal sheet that has an electric resistance value equivalent to that of the metal part of the connecting cable of the measuring device when measuring impedance, and for example, aluminum foil, metal tape, etc. can be used.
[0032] The impedance measuring device is an impedance analyzer, a network analyzer, a spectrum analyzer, etc., and is 1.0 x 10 7 Any device capable of measuring impedance in a frequency range up to 100 Hz may be used. Among these, it is preferable to measure the impedance using an impedance analyzer in the range of electrical resistance of electrophotographic members.
[0033] The conditions for measuring impedance are as follows. An impedance measuring device (for example, a 96W dielectric impedance measuring system with the product name "Solatron 1260" manufactured by Solartron) is used to measure impedance in the frequency range of 1.0 Hz. The measurement is performed in an environment with a temperature of 23°C and a relative humidity of 50%. The amplitude of the AC voltage is 1 Vpp. The electrophotographic member is divided into five equal regions in the longitudinal direction, and the above measurement is performed once in each region, for a total of five times. The average value is regarded as the impedance of the electrophotographic member. A more specific measurement procedure will be described later.
[0034] <Requirements (B)> Requirement (B) is a requirement that describes the state of the vicinity of the outer surface of the elastic layer. The vicinity of the outer surface refers to a 1 μm-thick region from the interface between the elastic layer and the surface layer to a position 1 μm deep into the elastic layer, and this region is designated as region A. Note that, as will be described later in requirement (C), region B inside the elastic layer excluding the outer surface refers to a 1 μm-thick region from the interface between the elastic layer and the surface layer to a position 5 μm to 6 μm deep into the elastic layer.
[0035] In a region of 5 μm or more in the depth direction from the interface between the elastic layer and the surface layer, including region B, the elastic layer has a matrix-domain structure in which domains made of a second phase containing a crosslinked product of a second rubber different from the first rubber and conductive particles are dispersed in a matrix made of an insulating first phase containing a crosslinked product of a first rubber. The ratio (AR22 / AR21) is 0.40 or less. Meanwhile, in region A near the outer surface of the elastic layer, the ratio (AR12 / AR11) is greater than 0.40. Region A does not have to have a matrix-domain structure in which domains made of a second phase are dispersed in a matrix made of the first phase, and may have an inverted structure in which the first phase is dispersed in the second phase.
[0036] In the matrix-domain structure, charges can be accumulated on the interface side with the matrix in the domain, and after the charges on the surface of the electrophotographic member are consumed by discharge, the charges accumulated in the domain are quickly transferred to the surface of the electrophotographic member. However, when the entire elastic layer has a matrix-domain structure, the charge transfer between the matrix part in the elastic layer and the conductive path of the electroconductive agent in the surface layer is not good at the interface between the surface layer and the elastic layer, and the charges stagnate. After the charges on the surface of the electrophotographic member are consumed by discharge, it becomes difficult to quickly transfer the charges to the surface of the electrophotographic member.
[0037] Therefore, the effect of applying a charge of the same polarity as the applied voltage to the contaminant at the contact portion between the electrophotographic member and the photoconductor (hereinafter also referred to as the "nip portion") after discharging upstream of the nip portion is not sufficiently obtained. As a result, the dischargeability of the contaminant to the photoconductor decreases, and the contaminant accumulates on the surface of the electrophotographic member. This phenomenon is likely to become evident in a high-speed process in which the time from discharge upstream to passing through the nip is short, or when there is a large amount of contaminant that needs to be charged.
[0038] In order to suppress the stagnation of charge transfer at the elastic layer / surface layer interface, it is preferable to have a configuration in which the amount of the second phase, which is the domain at the elastic layer / surface layer interface, is large. However, as will be described in detail later in Requirement (C), increasing the amount of domains throughout the elastic layer causes connections between the domains over a wide area, making it impossible to accumulate charges within the domains, and thus reducing the ability to impart charges to dirt substances.
[0039] For this reason, it is important that the amount of the second phase is large only in region A, which is near the outer surface of the elastic layer that forms the interface with the surface layer, and that the amount of the second phase in region B, which is the other elastic layer region, is an amount that allows the formation of domains in which the second phases are not connected to each other.
[0040] With the above-mentioned structure, the conductive paste formed by the electronic conductive agent in the surface layer flows from the second phase in the elastic layer. As a result, after the charge on the surface of the electrophotographic member is consumed by the discharge in the upstream portion of the nip, the charge can be transferred quickly to the surface of the electrophotographic member in the time it takes to reach the nip portion, and a sufficient charge can be applied to the soiling substance in the nip portion even in a high-speed main body in which the time is short.
[0041] Regarding the ratio of the second phase in the elastic layer on the outer surface of the elastic layer, a plane parallel to the longitudinal direction is cut out from the surface layer side of the electrophotographic member, and the surface of the elastic layer in region A is observed by a scanning electron microscope to calculate the area of the second phase. Specifically, when the sum of the areas of the first phase and the second phase, that is, the area of the entire first observation region is AR11 and the area of the domain is AR12, AR12 / AR11 must be greater than 0.40. AR12 / AR11 is preferably 0.50 to 0.75, and more preferably 0.60 to 0.75.
[0042] The thickness of the elastic layer is 10 μm or more. The thickness of the elastic layer is not particularly limited as long as it is 10 μm or more. The thickness of the elastic layer is preferably 1.0 mm to 2.0 mm.
[0043] <Requirements (C)> Requirement (C) is a requirement that expresses the state of the elastic layer in the region excluding the vicinity of the outer surface of the elastic layer. Specifically, it refers to a region from the elastic layer / surface layer interface to a depth of 5 μm or more in the depth direction of the elastic layer. The state of the second phase is observed in a representative region (region B) with a thickness of 1 μm from the elastic layer / surface layer interface to a position 5 μm to 6 μm in the depth direction of the elastic layer.
[0044] In a region of 5 μm or more in the depth direction from the interface between the elastic layer and the surface layer, including region B, the elastic layer has a matrix-domain structure in which domains are dispersed in the matrix. In region B, the ratio of the second phase (domain ratio) is 40% or less, that is, AR22 / AR21 is 0.40 or less.
[0045] When AR22 / AR21 is 0.40 or more, most of the domains may be connected to each other. When the domains are connected to each other, the phenomenon of charge transfer between the domains becomes dominant over the phenomenon of charge accumulation on the matrix interface side within the domain, and excessive discharge may occur upstream of the nip. Since charge cannot be accumulated on the matrix interface side within the domain, after the charge on the electrophotographic member surface is largely consumed by excessive discharge, charge cannot be quickly resupplied to the electrophotographic member surface, and sufficient charge cannot be applied to the contaminating substance at the nip. As a result, the contaminating substance cannot be sufficiently discharged to the photoconductor, and the accumulation of the contaminating substance becomes evident. In addition, white spots are likely to occur.
[0046] Regarding the ratio of the domains in region B, a plane parallel to the longitudinal direction is cut out from the surface layer side of the electrophotographic member, and any surface cut out in region B is observed by a scanning electron microscope to calculate the areas of the matrix portion and the domain portion. Specifically, when the sum of the areas of the matrix portion and the domain portion, that is, the area of the entire second observation region, is AR21, and the area of the second phase capable of forming a domain is AR22, AR22 / AR21 is 0.40 or less. AR22 / AR21 is preferably 0.15 to 0.40, and more preferably 0.20 to 0.40.
[0047] In addition, it is preferable that there are few convex or concave portions on the outer peripheral surface of the domains dispersed in the matrix in region B. When there are few convex or concave portions on the outer peripheral surface of the domains, charge transfer between the domains is less likely to occur, and charge is more uniformly supplied to the surface of the electrophotographic member. This is because charge transfer is concentrated on the convex portions, and when a portion where charge transfer is concentrated is created, the charge transfer is more uniform. As a result, it is possible to apply a charge more uniformly to the dirt, making it easier to prevent the accumulation of dirt. It is also easier to prevent white spots.
[0048] Specifically, the number of protrusions and recesses on the outer peripheral surface of a domain can be determined as follows: The second surface in region B is exposed, and an observation region of 15 μm square is placed at an arbitrary position on the second surface in region B using a scanning electron microscope, and the perimeter of the domain is defined as A, and the envelope perimeter of the domain is defined as B. In this case, the proportion of domains having an A / B value of 1.00 to 1.10 is preferably 80% by number or more, and more preferably 88 to 98% by number. The arithmetic mean value of A / B is preferably from 1.00 to 1.10, and more preferably from 1.00 to 1.07. Furthermore, when the second surface in region B is exposed and a 15 μm square observation area is placed at any position on the second surface in region B using a scanning electron microscope to observe the domains, the number-average circle equivalent diameter of the domains is preferably 0.2 to 3.0 μm, and more preferably 0.4 to 2.0 μm.
[0049] <Requirements (D)> Requirement (D) is a requirement for the surface layer. If there is no surface layer, the contact area between the toner and the elastic layer is very small, and if the contact area is the matrix part of the elastic layer, the charge imparted to the contaminant may be insufficient. Furthermore, if the surface layer is ionically conductive, it becomes more environmentally dependent, and sufficient conductivity cannot be obtained in low temperature and low humidity environments where excessive discharge due to contaminants is generally likely to occur, and since the charge response is slow, it is not possible to impart a sufficient charge to contaminants in a short period of time in a high-speed process, so the surface layer must contain an electronic conductive agent.
[0050] An electrophotographic member will be described with reference to Fig. 1, taking a conductive roller as an example. Fig. 1 is a cross-sectional view showing the configuration of a cross section perpendicular to the longitudinal direction, which is the axial direction, of the conductive roller. The conductive roller has a cylindrical substrate 11 having a conductive surface, an elastic layer 12 formed on the outer peripheral surface, i.e., the outer surface, of the substrate 11, and a surface layer 13 in contact with the surface of the elastic layer 12 opposite to the surface facing the substrate 11.
[0051] <Substrate (support) having a conductive surface> The material constituting the substrate 11 can be appropriately selected from materials known in the field of electroconductive members for electrophotography and materials usable as conductive members. Examples include metals or alloys such as aluminum, stainless steel, conductive synthetic resins, iron, and copper alloys.
[0052] Furthermore, the substrate may be subjected to an oxidation treatment or a plating treatment with chromium, nickel, or the like. As the type of plating, either electric plating or electroless plating can be used. From the viewpoint of dimensional stability, electroless plating is preferred. As the type of electroless plating used here, nickel plating, copper plating, gold plating, and various other alloy platings can be mentioned.
[0053] The plating thickness is preferably 0.05 μm or more, and considering the balance between work efficiency and rust prevention ability, the plating thickness is preferably 0.10 μm or more and 30.00 μm or less. The cylindrical shape of the base 11 may be a solid cylindrical shape or a hollow cylindrical shape (cylindrical shape). In addition, the outer diameter of the base is preferably in the range of 3 mm or more and 10 mm or less.
[0054] If necessary, the sheet is subjected to a partial processing for installation in an electrophotographic apparatus. If a medium resistance layer or an insulating layer is present between the substrate and the base, the charge may not be supplied promptly after the charge is consumed by discharge. Therefore, it is preferable to provide the elastic layer directly on the substrate, or to provide the elastic layer on the outer periphery of the substrate only via an intermediate layer made of a thin conductive resin layer such as a primer.
[0055] As the primer, a known one can be selected and used depending on the rubber material for forming the elastic layer and the material of the substrate, etc. Examples of the primer material include thermosetting resins and thermoplastic resins, and specifically, known materials such as phenolic resins, urethane resins, acrylic resins, polyester resins, polyether resins, and epoxy resins can be used.
[0056] <Elastic layer> The elastic layer includes an insulating first phase including at least a cross-linked product of a first rubber, and a second phase including a cross-linked product of a second rubber different from the first rubber and conductive particles. The elastic layer has a matrix-domain structure in which domains of the second phase are dispersed in a matrix of the first phase in a region of 5 μm or more in a depth direction from the interface between the elastic layer and the surface layer into the elastic layer. The details will be described later, but in order to satisfy requirement (B), the SP values ((J / cm) of the first rubber and the second rubber described above are set to 1000 to 15000 m. 3 ) 0.5 ) is preferably small, and the SP value difference is preferably 3.0 or less, more preferably 1.0 or less.
[0057] <Matrix> The matrix includes a first rubber. The volume resistivity ρm of the matrix in region B is 1.0×10 8 Ωcm or more 1.0×10 17 The volume resistivity of the matrix is preferably 1.0×10 8 By setting the resistivity at Ωcm or more, it is possible to suppress the matrix from disturbing the transfer of charges between conductive domains. 17 By setting the resistivity to Ωcm or less, discharge from the electrophotographic member to the member to be charged can be smoothly carried out when a charging bias is applied between the substrate and the member to be charged.
[0058] The volume resistivity of the matrix, ρm, is 1.0×10 8 Ωcm or more 1.0×10 15 Ωcm or less, even 1.0×10 8 Ωcm or more 1.0×10 14 The volume resistivity ρm of the matrix is preferably Ωcm or less. The method for measuring the volume resistivity ρm of the matrix will be described later. The volume resistivity ρm of the matrix can be controlled by the volume resistivity of the first rubber used in the matrix.
[0059] <First Rubber> The first rubber is the component with the highest compounding ratio in the rubber composition for forming the elastic layer, and the crosslinked product of the first rubber governs the mechanical strength of the elastic layer. Therefore, the first rubber used is one that exhibits the strength required for the electroconductive member for electrophotography after crosslinking in the elastic layer. Preferable examples of the first rubber are as follows: natural rubber (NR), isoprene rubber (IR), butadiene rubber (BR), styrene-butadiene rubber (SBR), butyl rubber (IIR), ethylene-propylene rubber (EPM), ethylene-propylene-diene terpolymer rubber (EPDM), chloroprene rubber (CR), acrylonitrile butadiene rubber (NBR), hydrogenated NBR (H-NBR), and silicone rubber.
[0060] The first rubber preferably includes at least one selected from the group consisting of isoprene rubber (IR), butadiene rubber (BR), styrene-butadiene rubber (SBR), and acrylonitrile butadiene rubber (NBR), and more preferably includes at least one selected from the group consisting of styrene-butadiene rubber (SBR) and acrylonitrile butadiene rubber (NBR).
[0061] The first rubber forming the matrix can contain a reinforcing material to the extent that it does not affect the electrical conductivity. An example of the reinforcing material is reinforcing carbon black with low electrical conductivity. Specific examples of reinforcing carbon black include FEF, GPF, SRF, and MT carbon.
[0062] Furthermore, the first rubber may contain, as necessary, fillers such as calcium carbonate, processing aids, vulcanization aids, vulcanization accelerators, vulcanization acceleration aids, vulcanization retarders, antioxidants, softeners, dispersants, colorants, etc.
[0063] <domain> The domain contains a crosslinked product of a second rubber different from the first rubber, and conductive particles. Here, the conductive property is defined as a volume resistivity of 1.0×10 8 The definition of insulating is that the volume resistivity is less than 1.0×10 8 Ωcm or more.
[0064] <Second Rubber> Specific examples of the second rubber include at least one selected from the group consisting of natural rubber (NR), isoprene rubber (IR), butadiene rubber (BR), acrylonitrile butadiene rubber (NBR), styrene butadiene rubber (SBR), butyl rubber (IIR), ethylene propylene rubber (EPM), ethylene propylene diene rubber (EPDM), chloroprene rubber (CR), nitrile rubber (NBR), hydrogenated nitrile rubber (H-NBR), silicone rubber, and urethane rubber (U).
[0065] The second rubber preferably includes at least one selected from the group consisting of isoprene rubber (IR), butadiene rubber (BR), styrene-butadiene rubber (SBR), acrylonitrile butadiene rubber (NBR), and ethylene propylene diene rubber (EPDM), and more preferably includes at least one selected from the group consisting of styrene-butadiene rubber (SBR), acrylonitrile butadiene rubber (NBR), and ethylene propylene diene rubber (EPDM).
[0066] <Conductive particles> Examples of conductive particles include carbon materials such as conductive carbon black and graphite, conductive oxides such as titanium oxide and tin oxide, metals such as Cu and Ag, and particles of electronic conductive agents such as particles that have been made conductive by coating the surface with a conductive oxide or metal. Two or more types of these conductive particles may be used in appropriate amounts.
[0067] The ratio S of the cross-sectional area of the conductive particles to the cross-sectional area of the domain in region B c / S is preferably 20.0 to 30.0%, and more preferably 25.0 to 30.0%. By densely packing the conductive particles in the domain in this way, it is easy to reduce the unevenness of the outer peripheral surface of the domain. There is no particular upper limit to the ratio of the cross-sectional area of the conductive particles to the cross-sectional area of the domain, but it is preferably 30.0% or less.
[0068] In order to obtain a domain in which the conductive particles are densely packed, it is preferable to use conductive carbon black as the conductive particles. That is, it is preferable that the conductive particles contain carbon black. The carbon black is preferably at least one selected from the group consisting of gas furnace black, oil furnace black, thermal black, lamp black, acetylene black, and ketjen black.
[0069] Among them, DBP absorption was 40 cm 3 / 100g or more 80cm 3 Carbon black having a DBP absorption capacity (cm3) of 100 g or less can be particularly preferably used. 3 / 100g) is the volume of dibutyl phthalate (DBP) that can be adsorbed by 100g of carbon black. It is measured according to the industrial standard (JIS) K6217-4:2017 (Carbon black for rubber - Basic properties - Part 4: Determination of oil absorption (including compressed samples)). Generally, carbon black has a cluster-like higher-order structure in which primary particles with an average particle size of 10 nm to 50 nm are aggregated. This cluster-like higher-order structure is called structure, and its degree is expressed by the DBP absorption (cm 3 / 100g).
[0070] Generally, carbon black with a developed structure has a high reinforcing effect on rubber, is difficult to incorporate into rubber, and has a very high shear torque during kneading, making it difficult to increase the amount of carbon black loaded in the domain. On the other hand, conductive carbon black with DBP absorption within the above range has a structure structure. Because the structure is underdeveloped, carbon black aggregates less and disperses well in rubber. Therefore, the amount of the particles packed in the domain can be increased, and as a result, the outer shape of the domain can be more easily made to be closer to a sphere.
[0071] Furthermore, carbon black with a developed structure tends to aggregate, and the aggregates tend to form lumps with large uneven structures. On the other hand, conductive carbon black with DBP absorption within the above range is preferred because it is less likely to form aggregates. The content of conductive particles such as conductive carbon black is preferably 20 parts by mass or more and 150 parts by mass or less relative to 100 parts by mass of the second rubber contained in the domain. More preferably, it is 50 parts by mass or more and 100 parts by mass or less.
[0072] The volume resistivity of the domain is 1.0×10 4 It is preferable to keep the resistance below 1.0×10 4 If the resistivity is Ωcm or less, the domain volume fraction that stably forms a matrix-domain structure can be made conductive. Note that the domain volume resistivity can be measured in the same manner as in the above-mentioned method for measuring the matrix volume resistivity, except that the measurement location is changed to a location equivalent to the domain and the applied voltage when measuring the current value is changed to 1V.
[0073] In order to obtain an electrophotographic member as specified in requirement (A), the average number of domains in a 15 μm square observation area placed in region B is preferably 20 to 300, more preferably 40 to 300. The observation area is a 15 μm square area placed in region B after cutting out flat surfaces parallel to the longitudinal direction of the electrophotographic member from the surface layer side at three positions, L1 / 4, L2 / 4, and L3 / 4, where L is the longitudinal length of the elastic layer. The arithmetic average value of these three observation areas is adopted. If the number of domains is 20 or more, sufficient conductivity is obtained for electrophotographic members, and sufficient charge supply can be achieved even in high-speed processes. If the number of domains is 300 or less, a sufficient inter-domain distance can be maintained, and aggregation of domains due to repeated image output can be suppressed, making it easy to achieve uniform discharge.
[0074] <Method of manufacturing elastic layer> The elastic layer of the electrophotographic member can be formed, for example, through a method including the following steps (i) to (iv). Step (i): A step of preparing a domain-forming rubber composition (hereinafter also referred to as "CMB") containing conductive particles and a second rubber. Step (ii): preparing a matrix-forming rubber composition (hereinafter also referred to as "MRC") containing a first rubber. Step (iii): A step of kneading the CMB and the MRC to prepare a rubber composition for forming an elastic layer having a matrix-domain structure. Step (iv): A step of forming an elastic layer by forming a layer of the rubber composition for forming an elastic layer prepared in step (iii) on a substrate directly or via another layer, and curing the layer of the rubber composition.
[0075] The mixing ratio of CMB and MRC in the rubber composition for forming the elastic layer (CMB:MRC) based on mass is preferably 10:90 to 40:60, more preferably 20:80 to 30:70. The rubber composition for forming the elastic layer may contain known additives such as vulcanizing agents and vulcanization accelerators as necessary. The elastic layer is, for example, a crosslinked product (vulcanizate) of the rubber composition for forming the elastic layer.
[0076] In order to obtain a domain that satisfies the requirement (C), the conductive particles used to prepare the CMB preferably have a DBP absorption of 40 cm 3 / 100g or more 170cm 3 / 100g or less, more preferably 40cm 3 / 100g or more 90cm 3 It is effective to add a large amount of carbon black having a carbon black content of 100 g or less to the second rubber and knead it to prepare the CMB. In this case, the amount of carbon black to be mixed with the second rubber in the CMB is preferably, for example, 40 parts by mass or more and 200 parts by mass or less per 100 parts by mass of the second rubber. In particular, it is 50 parts by mass or more and 100 parts by mass or less.
[0077] The ratio of the conductive particle cross section to the domain cross section within a domain may be measured as follows: First, a thin piece of the elastic layer is prepared. In order to favorably observe the matrix-domain structure, a pretreatment such as a dyeing treatment or a deposition treatment may be performed to favorably obtain a contrast between the conductive phase and the insulating phase.
[0078] The formed and pretreated thin section can be observed with a scanning electron microscope (SEM) or a transmission electron microscope (TEM). Among these, it is preferable to observe with an SEM at 1,000 to 100,000 magnifications in terms of the accuracy of quantifying the area of the domains that are the conductive phase. The above ratios can be obtained by binarizing and analyzing the obtained observation images using an image analyzer or the like. The specific procedure will be described later.
[0079] In order to further reduce the electric field concentration between the domains, it is preferable to make the outer shape of the domain closer to a sphere. To achieve this, it is preferable to control the domain diameter to be small. For example, in the process of preparing a rubber composition in which MRC and CMB are mixed and phase-separated to form a CMB domain in the MRC matrix, the domain diameter of the CMB is controlled to be small. By reducing the domain diameter of the CMB, the total specific surface area of the CMB increases, and the interface with the matrix increases, so that a tension that tries to reduce the tension acts on the interface of the CMB domain. As a result, the outer shape of the CMB domain becomes closer to a sphere. Therefore, it becomes easier to control the value of A / B to 1.00 to 1.10.
[0080] Here, the Taylor formula (formula (1)), Wu's empirical formula (formulas (2) and (3)), and Tokita's formula (formula (4)) are known to determine the domain diameter D in the matrix-domain structure formed when two incompatible polymers are melt-kneaded. (Sumitomo Chemical Technical Journal 2003-II, 42) Taylor's formula D=[C·σ / ηm·γ]·f(ηm / ηd) (1) ·Wu's Empirical Formula γ D ηm / σ = 4(ηd / ηm) 0.84 ηd / ηm>1 (2) γ D ηm / σ = 4(ηd / ηm) -0.84 ηd / ηm<1 (3)
[0081] ·Tokita's Ceremony
number
[0082] In equations (1) to (4), D is the domain diameter of the CMB (maximum Feret diameter Df), C is a constant, σ is the interfacial tension, ηm is the viscosity of the matrix, and ηd is the viscosity of the domain. In equation (4), γ is the shear rate, η is the viscosity of the mixture, P is the probability of collision and coalescence, φ is the domain phase volume, and EDK is the domain phase breakage energy.
[0083] From the above formulas (1) to (4), it is effective to control the physical properties of CMB and MRC and the kneading conditions in step (iii) in order to reduce the domain diameter D of CMB. Specifically, it is effective to control the following four items (a) to (d). (a) Difference in interfacial tension σ between the CMB and the MRC; (b) The ratio (ηm / ηd) of the viscosity of the CMB (ηd) and the viscosity of the MRC (ηm); (c) Shear rate (γ) and energy content (EDK) during kneading of CMB and MRC in step (iii); (d) Volume fraction of CMB in the mixture of CMB and MRC in step (iii)
[0084] (a) Interfacial tension difference between CMB and MRC Generally, when two incompatible rubbers are mixed, phase separation occurs. This is because the interaction between the same polymers is stronger than the interaction between different polymers, so the same polymers aggregate to lower the free energy and stabilize. The interface of the phase-separated structure comes into contact with different polymers, so the free energy is higher than the interior, which is stabilized by the interaction between the same molecules. As a result, in order to reduce the free energy of the interface, interfacial tension is generated that tries to reduce the area of contact with the different polymers. If this interfacial tension is small, the different polymers will tend to mix more uniformly in order to increase the entropy. The state of uniform mixing is dissolution, and the SP value, which is an indicator of solubility, tends to correlate with the interfacial tension. In other words, the difference in interfacial tension between CMB and MRC is thought to correlate with the SP value difference between CMB and MRC. Therefore, it is possible to control the combination of MRC and CMB, especially the combination of the first rubber and the second rubber.
[0085] For the first rubber in the MRC and the second rubber in the CMB, the absolute value of the difference in solubility parameter (SP value) between the first rubber and the second rubber is 0.4 to 5.7 (J / cm 3 ) 0.5 In particular, the absolute value of the difference in SP value is preferably 0.4 to 4.7 (J / cm 3 ) 0.5 It is preferable that the absolute value of the difference in the SP value is 0.4 to 3.0 (J / cm 3 ) 0.5 By using a combination of rubbers in which the absolute value of the difference in SP value falls within the above range, a phase separation structure can be formed more stably, and the domain diameter D of the CMB can be reduced. SP value of the first rubber (J / cm 3 ) 0.5 is preferably from 16.8 to 22.0, and more preferably from 17.0 to 21.7. SP value of the second rubber (J / cm 3 ) 0.5 is preferably from 15.8 to 22.0, more preferably from 16.0 to 20.0. As a preferable combination of the first rubber and the second rubber, on the premise that the absolute value of the difference in SP value is within the above range, for example, the following combinations can be mentioned. The first rubber is NBR and the second rubber is SBR; The first rubber is SBR and the second rubber is NBR; The first rubber is NBR and the second rubber is EPDM; The first rubber is SBR and the second rubber is EPDM; The first rubber is NBR and the second rubber is IR; or The first rubber is BR and the second rubber is NBR
[0086] <Method for Measuring SP Value> The SP values of the first rubber and the second rubber contained in each of MRC and CMB can be accurately calculated by creating a calibration curve using materials with known SP values. As these known SP values, the catalog values of material manufacturers can also be used. For example, for NBR and SBR, regardless of the molecular weight, the SP value is almost determined by the content ratio of acrylonitrile or styrene. Therefore, the rubbers constituting the matrix and the domain are analyzed for the content ratio of acrylonitrile or styrene using analytical methods such as pyrolysis gas chromatography (Py-GC) and solid NMR. Then, based on the calibration curve obtained from materials with known SP values, the SP value can be calculated based on the content ratio. Also, for isoprene rubber, the SP value is determined by the isomeric structure such as 1,2-polyisoprene, 1,3-polyisoprene, 3,4-polyisoprene, cis-1,4-polyisoprene, and trans-1,4-polyisoprene. Therefore, similar to SBR and NBR, the isomer content ratio is analyzed by Py-GC and solid NMR, etc., and the SP value can be calculated from materials with known SP values. The SP values of the materials with known SP values are those obtained by the Hansen sphere method.
[0087] (b) Viscosity Ratio of CMB and MRC The closer the viscosity ratio (ηd / ηm) between CMB and MRC is to 1, the smaller the maximum Feret diameter of the domains can be. The viscosity ratio between CMB and MRC can be adjusted by selecting the Mooney viscosity of CMB and MRC, and by mixing the type and amount of filler. It can also be adjusted by adding a plasticizer such as paraffin oil to an extent that does not interfere with the formation of a phase separation structure. The viscosity ratio can also be adjusted by adjusting the temperature during kneading. The viscosity of CMB and MRC is measured using the Mooney viscosity ML (1+4) It can be obtained by measuring the rubber temperature during kneading.
[0088] (c) Shear rate and energy during mixing of MRC and CMB The faster the shear rate during kneading of MRC and CMB, and the greater the amount of energy during shearing, the smaller the maximum Feret diameter Df of the domains can be.
[0089] The shear rate can be increased by increasing the inner diameter of the mixing member, such as the blade or screw of the mixer, decreasing the gap between the end face of the mixing member and the inner wall of the mixer, or by increasing the rotation speed. In addition, the energy during shear can be increased by increasing the rotation speed of the mixing member or by increasing the viscosity of the first rubber in the CMB and the second rubber in the MRC.
[0090] (d) Domain volume fraction (volume fraction of CMB in the mixture of CMB and MRC) The volume fraction of the CMB in the mixture of CMB and MRC correlates with the probability of the CMB colliding with the MRC. Specifically, the probability of the CMB colliding with the MRC decreases when the volume fraction of the CMB in the mixture of CMB and MRC is reduced. In other words, the domain size can be reduced by reducing the volume fraction of the domain in the elastic layer within the range where the required electrical conductivity is obtained.
[0091] <How to confirm matrix-domain (MD) structure> The matrix-domain structure can be confirmed, for example, by the following method. That is, a thin slice of the elastic layer is cut out from the elastic layer to prepare an observation sample. Examples of the means for cutting out the thin slice include a razor, a microtome, and an FIB. If necessary, the observation sample is subjected to a treatment (for example, a staining treatment or a deposition treatment) that can facilitate the distinction between the matrix and the domain. Then, the observation sample is subjected to a laser irradiation. Observe using a microscope, SEM or TEM. More specific procedures will be described later.
[0092] <Method of measuring domain perimeter, envelope perimeter, number of domains and average number of domains> The domain perimeter, envelope perimeter, and number of domains can be measured, for example, as follows. First, a slice is prepared in the same manner as in the measurement of the volume resistivity of the matrix described above. Then, a thin section having a fracture surface can be formed by means of a freeze fracture method, a cross polisher method, a focused ion beam (FIB) method, or the like. Considering the smoothness of the fracture surface and pretreatment for observation, the FIB method is preferred. In addition, in order to favorably observe the matrix-domain structure, a pretreatment such as a dyeing treatment or a deposition treatment may be performed to favorably obtain a contrast between the conductive phase and the insulating phase.
[0093] The formed and pretreated thin sections can be observed by SEM or TEM. Among these, it is preferable to observe with SEM at 1,000 to 100,000 magnifications in terms of the accuracy of quantifying the domain perimeter and envelope perimeter.
[0094] The domain perimeter, envelope perimeter, and number of domains can be measured by quantifying the images taken as described above. The fracture surface images obtained by SEM observation are processed using image processing software such as Image-Pro Plus (Planetron Corporation). The image is converted to an 8-bit grayscale image, and a monochrome image with 256 gradations is obtained. Next, the image is inverted to black and white, and binarized, so that the domains in the fracture surface become white. Next, the perimeter, envelope perimeter, and number of domains are calculated for each of the domain groups in the image. A more specific procedure will be described later.
[0095] For the above measurements, the sample is cut into pieces at three locations, namely, the center in the longitudinal direction and L / 4 (i.e., L1 / 4, L2 / 4, L3 / 4) from both ends toward the center, where L is the longitudinal length of the electrophotographic member. The cut pieces are then cut out from the surface layer side to form planes parallel to the longitudinal direction of the electrophotographic member, and the above observations are performed using planes in a depth region (region B) of 5 μm to 6 μm deep in the elastic layer direction from the elastic layer / surface layer interface.
[0096] In order to satisfy the requirement (B), it is preferable to aggregate domains in the vicinity of the outer surface of the elastic layer during the formation of the elastic layer in the step (iv) of forming the rubber composition for forming the elastic layer on the substrate. The method for this is described below.
[0097] 2 is a schematic diagram of a crosshead extruder 40. The crosshead extruder 40 is a device for evenly coating the entire circumference of a conductive substrate with the rubber composition for forming an elastic layer prepared in step (iii) to produce an unvulcanized rubber roller having a conductive substrate at its center.
[0098] The crosshead extrusion molding machine 40 is provided with a crosshead 44 to which the conductive substrate 41 and the rubber composition for forming an elastic layer 42 are fed, and a conveying roller 45 for feeding the conductive substrate 41 to the crosshead 44. Furthermore, a cylinder 46 for feeding the rubber composition for forming an elastic layer 42 to the crosshead 44 is provided.
[0099] The conveying roller 45 continuously feeds the plurality of conductive substrates 41 in the axial direction to the crosshead 44. The cylinder 46 has a screw 47 therein, and the rubber composition 42 for forming an elastic layer is fed into the crosshead 44 by the rotation of the screw 47.
[0100] When the conductive substrate 41 is fed into the crosshead 44, the entire circumference of the conductive substrate 41 is covered with the elastic layer forming rubber composition 42 fed into the crosshead from the cylinder 46. Then, the conductive substrate 41 is coated with the elastic layer forming rubber composition 42 on its surface from the die 48 at the exit of the crosshead 44. 2 is delivered as a coated unvulcanized rubber roller 43.
[0101] In crosshead extrusion molding, a tubular die is used at the tip of the crosshead to coat the rubber composition 42 for forming the elastic layer on the conductive substrate 41. The outer surface side of the rubber composition 42 for forming the elastic layer is subjected to friction with the inner wall of the die 48, and therefore receives a larger shear force when extruded than the area other than the outer surface. The shear force at the inner wall of the die is applied in the non-depth direction of the unvulcanized rubber roller, that is, in a direction parallel to the extrusion direction, so that the domain present on the outermost surface of the unvulcanized rubber roller is stretched in the non-depth direction.
[0102] In addition, the rubber composition compressed by the pressure applied by the extruder is released when it is extruded from the tip of the die, and the extruded rubber composition expands in the thickness direction (die swell effect). This expansion is affected by the shear rate, and the higher the shear rate, the greater the expansion when the pressure is released. The faster the flow rate of the rubber, the greater the shear rate. The rubber flow rate is slower at the die wall due to friction between the wall and the flowing rubber, so the rubber expands less after extrusion. On the other hand, the rubber flowing in the area inside the outer surface, which has no friction with the wall, expands more after extrusion because the rubber flow rate is faster. Therefore, after extrusion, a domain transition occurs from the inner area where the expansion is large to the outer surface side where the expansion is small.
[0103] The domains are stretched in the non-depth direction at the inner wall of the die and migrate to the outer surface of the domains when extruded from the die, causing aggregation of the domains near the outer surface of the rubber composition for forming the elastic layer, which makes it possible to form an elastic layer that satisfies requirement (B).
[0104] The phenomenon in which the domains are stretched and the phenomenon in which the domains migrate to the outer surface become evident by reducing the inner diameter of the die or increasing the flow rate of the rubber during extrusion, and are therefore more preferable production conditions.
[0105] Moreover, the smaller the domain size, the more noticeable the migration of the domain to the outer surface. In order to reduce the domain size, there is a method of reducing the difference in the SP value between the first rubber in the matrix and the second rubber in the domain. Therefore, as mentioned above, it is more preferable to use a rubber that reduces the difference in the SP value between the two.
[0106] The volume resistivity of region A is ρ A , the volume resistivity of region B is ρ B Then, ρ B / ρ A It is preferable that ρ is ≧10.0. B / ρ A More preferably, ρ is 30.0 to 90.0. B / ρ A When the thickness is in the above range, it is possible to suppress the stagnation of charge transfer at the elastic layer / surface layer interface. ρ B / ρ A can be controlled within the above range by the same method as the method for transferring the domain to the outer surface of the elastic layer to satisfy the requirement (B).
[0107] <Surface layer> The surface layer contains an electronic conductive agent. When the surface layer is formed in a form in which the electronic conductive agent is dispersed and contained in the binder resin, the dispersion proceeds sufficiently, and this is also preferable in terms of the physical durability of the surface layer. In other words, the surface layer preferably contains a binder resin and an electronic conductive agent dispersed in the binder resin. The surface layer may contain roughening particles, a surface release agent, etc., as necessary.
[0108] <Electronic conductive agent> Examples of the electronic conductive agent contained in the surface layer include conductive particles such as conductive carbon black, metal oxide-based conductive particles such as titanium oxide, tin oxide, and zinc oxide, and metal-based conductive particles such as aluminum, iron, copper, and silver. In other words, the electronic conductive agent is a conductive particle. These conductive particles may be used alone or in combination of two or more kinds.
[0109] In addition, composite particles in which silica particles are coated with conductive particles can also be used as the conductive particles. The conductive particles used in the surface layer preferably contain carbon black. Carbon black has a low specific gravity and high conductivity, so that a small amount of carbon black added to the binder resin can ensure sufficient conductivity for the surface layer. In the present disclosure, it is preferable to keep the hardness of the surface layer low, so carbon black suitable for small addition is suitable. The content of the electronic conductive agent is preferably 10 to 40 parts by mass, and more preferably 15 to 30 parts by mass, based on 100 parts by mass of the binder resin.
[0110] <Binder resin> As the binder resin, known binder resins can be used. For example, various synthetic resins, natural rubber and its vulcanized products, synthetic rubber, and other rubbers can be used. As the binder resin, fluororesin, polyamide resin, acrylic resin, polyurethane resin, silicone resin, butyral resin, styrene-ethylene / butylene-olefin copolymer, olefin-ethylene / butylene-olefin copolymer, and the like can be used.
[0111] The binder resins may be used alone or in combination of two or more kinds. The binder resin preferably contains a polyurethane resin, which is preferably at least one selected from the group consisting of polyester-based polyurethanes obtained by copolymerizing polyester polyols and polyisocyanates, polycarbonate-based polyurethanes obtained by copolymerizing polycarbonate polyols and polyisocyanates, and polyurethanes obtained by copolymerizing ε-caprolactone-modified polyols and polyisocyanates.
[0112] Among these, the binder resin is preferably a resin containing a polycarbonate structure in order to achieve both flexibility by reducing the universal hardness of the surface layer and high resistance of the surface layer. The polycarbonate structure has low polarity, so that the volume resistivity of the binder resin itself can be kept high. Specifically, a polycarbonate-based polyurethane obtained by copolymerizing polycarbonate polyol and polyisocyanate is preferable.
[0113] Examples of polycarbonate polyols include polynonamethylene carbonate diol, poly(2-methyl-octamethylene) carbonate diol, polyhexamethylene carbonate diol, polypentamethylene carbonate diol, poly(3-methylpentamethylene) carbonate diol, polytetramethylene carbonate diol, polytrimethylene carbonate diol, poly(1,4-cyclohexanedimethylene carbonate) diol, poly(2-ethyl-2-butyl-trimethylene) carbonate diol, and random / block copolymers thereof.
[0114] The polyisocyanate is selected from commonly used known ones, for example, toluene diisocyanate (TDI), diphenylmethane diisocyanate (MDI), polymeric diphenylmethane polyisocyanate, hydrogenated MDI, xylylene diisocyanate (XDI), hexamethylene diisocyanate (HDI), isophorone diisocyanate (IPDI), etc. Among these, aromatic isocyanates such as toluene diisocyanate (TDI), diphenylmethane diisocyanate (MDI), and polymeric diphenylmethane polyisocyanate are more preferably used.
[0115] <Universal hardness of surface layer> In order to suppress the generation of contaminants, it is effective to prevent the toner from cracking or deforming. For this purpose, it is preferable that the surface layer is flexible. The universal hardness at a depth of 1 μm from the outer surface of the surface layer ("Universal hardness (t=1 μm position)") is 1.0 to 7.0 N / mm 2 It is preferable that the resistance is 2.0 to 5.0 N / mm 2 It is more preferable that:
[0116] Since the size of the external additives and toner is on the order of submicrons to several microns, it is preferable to control the hardness in the immediate vicinity of the outer surface, which is the surface of the surface layer that comes into contact with the external additives and toner. Specifically, the universal hardness of the surface at the time when the indenter is pressed 1 μm from the outer surface of the surface layer is 1.0 N / mm 2 By setting the universal hardness at 7.0 N / mm or more, it is easy to suppress the occurrence of image density unevenness due to the deformation of the charging roller that occurs when the charging roller is in contact with the electrophotographic photosensitive member in a stationary state for a long period of time. 2 By setting the above, deformation and cracking of the toner can be suppressed, and therefore the absolute amount of irregular toner and finely powdered toner remaining on the photoconductor can be more reliably suppressed.
[0117] Furthermore, the universal hardness is 5.0N / mm 2By setting it as follows, the surface layer will deform in response to the dirt substance, so that the number of contact points between the convex parts of the electronic conductive agent exposed on the surface of the surface layer and the dirt substance will increase, improving the efficiency of electron injection from the convex parts to the dirt substance. The universal hardness (at t=1 μm) can be controlled by the molecular weight of the polyol component and the ratio of the polyol component and the polyisocyanate component.
[0118] The universal hardness of the surface of the surface layer of the charging roller is measured, for example, using a universal hardness tester (product name: Fischerscope HM2000XYp, manufactured by Fisher Instruments). The universal hardness is a physical property value that is determined by pressing an indenter into a measurement object while applying a load, and is expressed as "(test load) / (surface area of indenter under test load) (N / mm 2 A square pyramid or other indenter is pressed into the test object while applying a relatively small predetermined test load, and the surface area in contact with the indenter is calculated from the indentation depth at the point where a predetermined indentation depth is reached, and the universal hardness is calculated using the above formula.
[0119] The universal hardness of the surface of the surface layer of the charging roller is measured, for example, using a universal hardness tester (product name: Fischerscope HM2000XYp, manufactured by Fisher Instruments). The universal hardness is a physical property value that is determined by pressing an indenter into a measurement object while applying a load, and is expressed as "(test load) / (surface area of indenter under test load) (N / mm 2 The universal hardness is calculated as "the surface area of the material that is in contact with the indenter, measured by the depth of the indenter when the indenter reaches a certain depth, and the universal hardness is calculated from the above formula. A more specific procedure will be described later.
[0120] <Surface layer protrusions derived from electronic conductive agent> In order to inject charges into the contaminants, it is preferable that there are convex portions on the surface of the surface layer originating from the exposed portions of the electronic conductive agent (conductive particles). The size of the convex portions originating from the exposed portions of the electronic conductive agent is preferably 5.0 nm or more and 100.0 nm or less. By making the size 5.0 nm or more, the convex portions can function as starting points for more efficiently injecting charges into the contaminants. In addition, by making the size 100.0 nm or less, it is possible to suppress excessive injection of charges into the photoconductor. Note that the size of the convex portions means the average particle diameter (number average particle diameter) of the particle diameter 303 of the electronic conductive agent 301 in the portion exposed from the binder resin 302, as shown in FIG. 9. The method for measuring the size of the convex portions is to take an image of an arbitrary 2 μm square area using a SEM, measure the particle diameters of 20 particles randomly selected from the obtained image, and obtain the arithmetic average particle diameter.
[0121] It is also preferable that the outer surface of the surface layer has protrusions resulting from the exposed portions of the electronic conductive agent. In order to inject electric charges into the dirt using the protrusions derived from the electronic conductive agent, it is effective to control the number of protrusions. The number of protrusions derived from the exposed part of the electronic conductive agent is set to an area of 2.0 μm in length and 2.0 μm in width (4.0 μm 2 In the region, the number is preferably 50 to 500, and more preferably 200 to 400. By making the number 50 or more, the number of protrusions as starting points for injecting electric charge into the dirt substance can be secured. Furthermore, by making the number 500 or less, the injection of electric charge into the photoconductor can be suppressed. The number of protrusions can be calculated by taking an image of any 2 μm square region using a scanning electron microscope (SEM) and calculating the number of conductive points from the binarized image.
[0122] Next, a method for exposing the electronic conductive agent (conductive particles) on the surface of the surface layer will be described. When a surface layer is formed on the elastic layer of an electrophotographic member by a dip coating method, a skin layer is necessarily formed on the outermost surface of the surface layer. Therefore, in order to expose the electronic conductive agent on the outer surface of the surface layer and generate convex portions on the outer surface of the surface layer by the exposed portion, it is effective to remove the outermost skin layer.
[0123] For example, by performing ultraviolet treatment, polishing, electrolytic polishing, chemical polishing, ion milling, etc., the surface skin layer made of the binder resin is removed, the electronic conductive agent is exposed on the outer surface of the surface layer, and the convex portion is easily formed. In the present disclosure, since the hardness of the surface layer is low, the skin layer can be sufficiently removed and the electronic conductive agent can be exposed on the surface of the surface layer even by performing ultraviolet treatment. Compared with polishing methods, etc., ultraviolet treatment is preferable because it can expose the electronic conductive agent on the surface of the surface layer while minimizing damage to the surface layer.
[0124] The exposed state of the electronic conductive agent can be confirmed using an atomic force microscope (AFM). A height image is acquired in tapping mode of the AFM. In this case, the part originating from the exposed part of the electronic conductive agent is confirmed as a convex part. When a height image is acquired in a state where a skin layer is present after dip coating, the convex part is not confirmed. Furthermore, a phase image is acquired in tapping mode of the AFM. In this case, the phase shift of the electronic conductive agent is small, and an image with a very large contrast difference between light and dark is obtained due to the hardness difference between the binder resin and the electronic conductive agent. When a phase image is acquired in a state where a skin layer is present after dip coating, an image with very few phase differences and low contrast differences is obtained.
[0125] <Roughening particles> The surface layer may contain roughening particles to the extent that the effect of the present disclosure is not impaired. Examples of the roughening particles include the following: organic insulating particles such as acrylic resin, polycarbonate resin, styrene resin, urethane resin, fluororesin, and silicone resin; and inorganic insulating particles such as titanium oxide, silica, alumina, magnesium oxide, strontium titanate, barium titanate, barium sulfate, calcium carbonate, mica, zeolite, and bentonite.
[0126] In the present disclosure, it is preferable to use flexible organic insulating particles as the roughening particles, since the surface layer is deformed to increase the contact opportunity with external additives, toner, and other contaminants. These particles may be used alone or in combination of two or more. The number-average particle diameter of the roughening particles is not particularly limited, but is about 3 μm or more and 30 μm or less.
[0127] <Ionic conductive agent> The surface layer may contain an ionic conductive agent to the extent that the effect of the present disclosure is not impaired. In order to transport the charge to be supplied to the attached dirt from the elastic layer, it is necessary for the surface layer to contain an electronic conductive agent with good response, but an ionic conductive agent with a relatively low (slow) response may be added as an auxiliary. This allows the charge that can be supplied to the dirt on the surface at a certain moment to be determined by the electronic conductive agent. The charge transported from the elastic layer by the ionic conductive agent is added to the charge transported from the elastic layer by the ionic conductive agent. Therefore, the possibility of insufficient charge supply is further reduced when the charge transport is mainly performed by the electronic conductive agent.
[0128] The ionic conductive agent is not particularly limited as long as it exhibits ionic conductivity, and examples thereof include the following: inorganic ionic substances such as lithium perchlorate, sodium perchlorate, and calcium perchlorate; quaternary ammonium salts such as lauryl trimethyl ammonium chloride, stearyl trimethyl ammonium chloride, and tetrabutyl ammonium perchlorate; inorganic salts of organic acids such as lithium trifluoromethanesulfonate and potassium perfluorobutanesulfonate; and the like. These can be used alone or in combination of two or more kinds.
[0129] Among ionic conductive agents, those having a functional group that easily forms a bond with the material that constitutes the surface layer are preferred because the ionic conductive agent is fixed inside the surface layer and therefore tends to maintain its characteristics for a long time. For example, when a urethane bond is present in the surface layer, the ionic conductive agent has an OH group. More preferably, the ionic conductive agent has an imidazolium structure in its structure. Since the charge is easily delocalized on the imidazolium ring and charge uneven distribution within the structure is unlikely to occur, uniform charge transfer within the surface layer and more uniform charge supply to dirt can be expected.
[0130] Since the ionic conductive agent is used to play a supplementary role to the electronic conductive agent, the amount of the ionic conductive agent is less than that of the electronic conductive agent constituting the surface layer, and is preferably 0.01 to 5.0 parts by mass, more preferably 0.01 to 2.0 parts by mass, relative to 100 parts by mass of the binder resin.
[0131] <Other additives> Other additives may be added to the surface layer as necessary, provided that the effects of the present disclosure are not impaired. Examples of additives include chain extenders, crosslinkers, pigments, silicone additives, and catalysts such as amines and tin complexes. When a silicone additive is added to the surface layer, it is particularly preferable to add the silicone additive because it increases the resistance of the surface layer, imparts slipperiness to the surface layer, suppresses the injection of charges into the photoreceptor, and improves the wear resistance of the surface layer.
[0132] <Thickness of surface layer> The surface layer preferably has a thickness of 0.1 to 100 μm. The thickness of the surface layer is more preferably 1 to 50 μm, further preferably 5 to 30 μm, and further more preferably 10 to 30 nm. The thickness of the surface layer can be measured by cutting out the cross section of the roller with a sharp blade and observing it with an optical microscope or an electron microscope.
[0133] <Volume resistivity of surface layer> When the electrophotographic member is used as a charging roller, the volume resistivity of the surface layer of the charging roller is 1.0×10 10 ~1.0×10 16Ω·cm is preferable. More preferably, 5.0×10 10 ~1.0×10 16 It is Ω·cm. When using an electrophotographic member as a charging roller, it is preferable to make the volume resistivity of the surface layer a large value. By increasing the volume resistivity of the surface layer, contaminants can be easily returned to the photoreceptor, and the amount of contaminants that accumulate on the charging roller can be further reduced.
[0134] The present inventors believe that when negatively charged soiling substances come into direct contact with the surface layer, particularly with a binder resin in which the electronic conductive agent (conductive particles) is not exposed on the surface, the negative charge of the soiling substances may move to the surface layer side of the charging roller, and the negative charge of the soiling substances may decay. In order to suppress the decay of the negative charge of the soiling substances, it is preferable that the surface layer has a high resistance, and for this purpose, the volume resistivity of the surface layer is set to 1.0×10 10 It is preferable to set it to Ω·cm or more.
[0135] The inventors have also confirmed that when the volume resistivity of the surface layer is low, charge is injected from the charging roller to the photoconductor. This phenomenon becomes more pronounced when the hardness of the surface layer is low and when a difference in peripheral speed is provided between the charging roller and the photoconductor. During actual image output, the injected charge amount is added to the charge amount due to discharge, so when the injected charge amount is large, it may be difficult to keep the surface potential of the photoconductor stable. The target injected charge amount for maintaining output with a stable image density is 50 V or less, and to achieve this, the volume resistivity of the surface layer must be set to 1.0 x 10 10 It is more preferable to set it to Ω·cm or higher.
[0136] In order to stabilize the discharge as a charging roller, the volume resistivity of the surface layer is set to 1.0×10 16 It is preferable that the resistivity is Ω·cm or less. The amount of charge injected from the charging roller to the photoconductor can be estimated, for example, as follows.
[0137] The surface potential of the photoconductor is measured when a voltage is applied to the charging roller (for example, DC-500V) under conditions where the charging roller does not discharge under a high temperature and high humidity environment (temperature 30°C, relative humidity 80%) where the injected charge amount increases. The volume resistivity of the surface layer can be measured using an atomic force microscope (AFM) in a conductive mode. A sheet is cut out from the surface layer of the charging roller using a manipulator, and metal deposition is performed on one side of the surface layer. A DC power source is connected to the surface on which metal deposition is performed, a voltage is applied, and the free end of a cantilever is brought into contact with the other side of the surface layer, and a current image is obtained through the AFM main body. The current value at 100 randomly selected points on the surface is measured, and the volume resistivity can be calculated from the average current value of the top 10 points with the lowest measured current value, the average film thickness, and the contact area of the cantilever.
[0138] <Method of manufacturing surface layer> The method for forming the surface layer is not particularly limited, but includes spraying, immersion (dipping coating method), or roll coating using a paint containing a solvent added to the raw material. The dip coating method is a simple method for forming the surface layer and has excellent production stability. In addition, additional treatment such as heating is performed as necessary after coating. The method for manufacturing the surface layer preferably includes a step of applying a paint containing raw materials including a binder resin raw material and an electronic conductive agent to the outer surface of the elastic layer, and a step of curing the raw material of the binder resin to form the surface layer.
[0139] <Process cartridge> At least one aspect of the present disclosure provides a process cartridge including the electrophotographic member of the present disclosure. Fig. 3 is a schematic cross-sectional view of an electrophotographic process cartridge 100 including the electrophotographic member according to one embodiment of the present disclosure as a charging roller. This process cartridge is configured to be detachably attached to the main body of an electrophotographic image forming apparatus by integrating a developing device and a charging device.
[0140] The developing device is an integrated unit of at least a developing roller 103, a toner container 106, and a toner 109, and may also include a toner supply roller 104, a developing blade 108, and an agitating blade 110 as necessary.
[0141] The charging device is an integrated device of at least the photosensitive drum 101 and the charging roller 102, and may include a cleaning blade 105 and a waste toner container 107. The charging roller 102, the developing roller 103, the toner supply roller 104, and the developing blade 108 are each configured to have a voltage applied thereto.
[0142] In addition, the electrophotographic member according to the present disclosure can be used as a charging roller, a developing roller, a developing blade, and a toner supply roller. The electrophotographic member is preferably a charging member, and more preferably the electrophotographic member is a charging roller.
[0143] <Electrophotographic image forming apparatus> At least one aspect of the present disclosure provides an electrophotographic image forming apparatus including the electrophotographic member of the present disclosure. Fig. 4 is a schematic diagram of an electrophotographic image forming apparatus 200 using the electrophotographic member according to one embodiment of the present disclosure as a charging roller. This apparatus is a color electrophotographic apparatus in which the process cartridge 100 is detachably mounted. Each process cartridge uses toner of each color: black BK, magenta M, yellow Y, and cyan C.
[0144] The photosensitive drum 201 rotates in the direction of the arrow, is uniformly charged by a charging roller 202 to which a voltage is applied from a charging bias power supply, and an electrostatic latent image is formed on the surface by exposure light 211. Meanwhile, toner 209 stored in a toner container 206 is supplied to a toner supply roller 204 by an agitating blade 210 and transported onto a developing roller 203. Then, the toner 209 is uniformly coated on the surface of the developing roller 203 by a developing blade 208 arranged in contact with the developing roller 203, and the toner 209 is charged by frictional charging. The electrostatic latent image is developed by the toner 209 transported by the developing roller 203 arranged in contact with the photosensitive drum 201, and is visualized as a toner image.
[0145] The visualized toner image on the photosensitive drum is transferred by a primary transfer roller 212 to which a voltage is applied by a primary transfer bias power supply, onto an intermediate transfer belt 215 supported and driven by a tension roller 213 and an intermediate transfer belt drive roller 214. The toner images of each color are superimposed in order to form a color image on the intermediate transfer belt.
[0146] A transfer material 219 is fed into the apparatus by a paper feed roller, and is transported between an intermediate transfer belt 215 and a secondary transfer roller 216. A voltage is applied to the secondary transfer roller 216 from a secondary transfer bias power supply, and the secondary transfer roller 216 transfers the color image on the intermediate transfer belt 215 onto the transfer material 219. The transfer material 219 onto which the color image has been transferred is fixed by a fixing device 218, and is then discarded outside the apparatus, completing the printing operation.
[0147] Meanwhile, the toner remaining on the photosensitive drum without being transferred is scraped off by a cleaning blade 205 and stored in a waste toner storage container 207, and the above-mentioned process is repeated for the cleaned photosensitive drum 201. In addition, the toner remaining on the primary transfer belt without being transferred is also scraped off by a cleaning device 217.
[0148] Although a color electrophotographic device is shown as an example, in a monochrome electrophotographic device (not shown), the process cartridge uses only black toner. A monochrome image is formed directly on the transfer material by the process cartridge and the primary transfer roller (no secondary transfer roller) without the intermediate transfer belt. The image is then fixed by the fixing device and the paper is discharged outside the device, completing the printing operation. EXAMPLES
[0149] The present disclosure will be described below based on examples, but the technical scope of the present disclosure is not limited to these.
[0150] The charging members in the present disclosure were prepared using the materials shown below. <Elastic layer forming material> <nbr> NBR (1) (Product name: JSR NBR N230SV, acrylonitrile content: 35%, Mooney viscosity ML) (1+4) 100℃: 32, SP value: 20.0 (J / cm 3 ) 0.5 , manufactured by JSR, abbreviation: N230SV) NBR (2) (Product name: Nipol DN401LL, acrylonitrile content: 18.0%, Mooney viscosity ML (1+4) 100℃: 32, SP value: 17.4 (J / cm 3 ) 0.5 , manufactured by Zeon Corporation, abbreviation: DN401LL) NBR (3) (Product name: JSR NBR N215SL, acrylonitrile content: 48%, Mooney viscosity ML) (1+4) 100℃: 45, SP value: 21.7 (J / cm 3 ) 0.5 , manufactured by JSR, abbreviation: N215SL)
[0151] <sbr> SBR (1) (product name: Tufden 2000R, styrene content: 25%, Mooney viscosity ML (1+4) 100℃: 45SP value: 17.0 (J / cm 3 ) 0.5 , manufactured by Asahi Kasei Corporation, abbreviation: T2000R) SBR (2) (product name: Tufden 2003, styrene content: 25%, Mooney viscosity ML) (1+4) 100℃: 33, SP value: 17.0 (J / cm 3 ) 0.5 , manufactured by Asahi Kasei Corporation, abbreviation: T2003)
[0152] <epdm> EPDM (product name: Esprene505A, Mooney viscosity ML (1+4) 100℃: 47, SP value: 16.0 (J / cm 3 ) 0.5 (Manufactured by Sumitomo Chemical Co., Ltd., abbreviation: E505A)
[0153] <Butadiene rubber BR> Butadiene rubber (product name: UBEPOL BR130B, Mooney viscosity ML) (1+4) 100℃: 29, SP value: 16.8 (J / cm 3 ) 0.5 , manufactured by Ube Industries, abbreviation: BR130B)
[0154] <Isoprene rubber IR> Isoprene rubber (product name: Nipol 2200L, Mooney viscosity ML) (1+4) 100℃: 70, SP value: 16.5 (J / cm 3 ) 0.5 , manufactured by Zeon Corporation, abbreviation: IR2200L)
[0155] <Conductive particles> Carbon black (1) (Product name: Toka Black #7270SB, DBP absorption capacity: 62 cm 3 / 100g, Tokai Carbon Co., Ltd., abbreviation: #7270) Carbon black (2) (Product name: Toka Black #7360SB, DBP absorption capacity: 87 cm 3 / 100g, manufactured by Tokai Carbon Co., Ltd., abbreviation: #7360) Carbon black (3) (product name: Toka Black #5500, DBP absorption capacity: 155 cm 3 / 100g, manufactured by Tokai Carbon Co., Ltd., abbreviation: #5500) Carbon black (4) (Product name: Raven 1170, DBP absorption capacity: 55 cm 3 / 100g, manufactured by Columbia Chemical Co., abbreviation: R1170) Carbon black (5) (product name: MA100, DBP absorption capacity: 95 cm 3 / 100g, manufactured by Mitsubishi Chemical Corporation, abbreviation: MA100)
[0156] <Vulcanizing agent> Vulcanizing agent (product name: SULFAX PMC, sulfur content 97.5%, manufactured by Tsurumi Chemical Industry Co., Ltd., abbreviation: sulfur)
[0157] <Vulcanization accelerator> Vulcanization accelerator (1) (product name: Suncerer TBZTD, tetrabenzyl thiuram disulfide, manufactured by Sanshin Chemical Industry Co., Ltd., abbreviation: TBzTD) Vulcanization accelerator (2) (trade name: SANTOCURE-TBSI, Nt-butyl-2-benzothiazole sulfenimide, manufactured by FLEXSYS, abbreviation: TBSI) Vulcanization accelerator (3) (product name: Noccela EP-60, vulcanization accelerator mixture, manufactured by Ouchi Shinko Chemical Industry Co., Ltd., abbreviation: EP-60) Vulcanization accelerator (4) (trade name: Noccela TBT, tetrabutyl thiuram disulfide, manufactured by Ouchi Shinko Chemical Industry Co., Ltd., abbreviation: TBT)
[0158] <Filling agent> Filler (1) (product name: Nanox #30, calcium carbonate, manufactured by Maruo Calcium Co., Ltd., abbreviation: #30) Filler (2) (Thermax Flowform N990, manufactured by CanCab, abbreviation: MT)
[0159] <Surface layer forming material> A-1: Polyester polyol (product name: P2010, manufactured by Kuraray Co., Ltd.) A-2: Polycarbonate polyol (product name: T5652, manufactured by Asahi Kasei Chemicals Corporation) A-3: ε-caprolactone modified polyol (product name: DC2016, manufactured by Daicel Chemical Industries, Ltd.)
[0160] B-3: Isocyanate A / Isocyanate B=4:3 (Product name: Bestanat B1370, manufactured by Degussa Corporation / Product name: Duranate TPA-880E, manufactured by Asahi Kasei Chemicals Corporation)
[0161] C-1: Urethane particles (product name: Dimic Beads UCN-5070D, average particle size 7.0 μm, manufactured by Dainichiseika Color & Chemicals Co., Ltd.) C-2: PMMA particles (product name: Ganzpearl GM0801, average particle size 8.0 μm, manufactured by Aica Kogyo Co., Ltd.) CB: Conductive carbon black (product name: MA230, manufactured by Mitsubishi Chemical Corporation, number average particle size 30 nm) D-1: Modified dimethyl silicone oil (product name: SH-28PA, manufactured by Toray Dow Corning Silicone Co., Ltd.)
[0162] <Example 1> <Preparation of charging roller 1> [1-1. Preparation of domain-forming rubber composition (CMB)] A rubber composition for domain formation (CMB) was obtained by mixing the materials of the types and amounts shown in Table 1 in a pressure kneader. The mixing conditions were a filling rate of 70 vol%, a blade rotation speed of 30 rpm, and 18 minutes.
[0163] [Table 1]
[0164] [1-2. Preparation of matrix-forming rubber composition (MRC)] A matrix-forming rubber composition (MRC) was obtained by mixing the materials of the types and amounts shown in Table 2 in a pressure kneader. The mixing conditions were a filling rate of 70 vol%, a blade rotation speed of 30 rpm, and 18 minutes.
[0165] [Table 2]
[0166] [1-3. Preparation of rubber composition 1 for forming elastic layer] The materials of the types and amounts shown in Table 3 were mixed with an open roll to prepare rubber composition 1 for forming elastic layer. An open roll with a roll diameter of 12 inches was used as the mixer. The mixing conditions were a front roll rotation speed of 10 rpm, a rear roll rotation speed of 8 rpm, a roll gap of 2 mm, and a total of 20 left and right turns, followed by 10 thin passes with a roll gap of 1.0 mm.
[0167] [Table 3]
[0168] [1-4. Forming of conductive elastic roller 1] A round bar with a total length of 252 mm and an outer diameter of 6 mm was prepared, the surface of which was made of free-cutting steel and electroless nickel plating was applied. Next, an adhesive (product name: Metalock U-20, manufactured by Toyo Kagaku Kenkyusho) was applied using a roll coater over the entire circumference of the round bar, excluding 11 mm at each end, over a range of 230 mm, to prepare a substrate.
[0169] Next, the elastic layer forming rubber composition 1 was applied to the substrate using a crosshead extruder (manufactured by Mitsuba Manufacturing Co., Ltd.) to produce a crown-shaped unvulcanized rubber roller. A die with an inner diameter of 9.6 mm was attached to the tip of the crosshead. The molding temperatures of the cylinder, screw, and crosshead were each set to 100°C. The transport speed of the substrate was changed to form a crown shape, but the arithmetic average speed when molding one charging roller was adjusted to 47 mm / sec. At the die exit, the conductive rubber flows out at the same speed as the core metal, so the arithmetic average speed when molding one roller was adjusted to 47 mm / sec. The average flow velocity during this process is 47 mm / sec, which is the same as the transport speed of the substrate. The screw rotation speed was adjusted so that the outer diameter of the unvulcanized rubber roller was 9.8 mm at the longitudinal center with respect to the transport speed of the substrate. The molded unvulcanized rubber roller had a crown shape, with the outer diameter at the longitudinal center being 9.8 mm and the outer diameter at positions 90 mm away from the longitudinal center to both ends being 9.7 mm.
[0170] The unvulcanized rubber roller was then vulcanized by heating in an electric furnace at a temperature of 160° C. for 60 minutes, and both ends were cut to produce a conductive elastic roller 1 with the length of the conductive rubber formed in the axial direction being 232 mm.
[0171] [2-1. Preparation of Coating Solution 1 for Surface Layer] A surface layer coating solution 1 for forming the surface layer 1 was prepared as follows. Under a nitrogen atmosphere, 100 parts by mass of polyester polyol (product name: P3010, manufactured by Kuraray Co., Ltd.) was gradually added dropwise to 27 parts by mass of polymeric MDI (product name: Millionate MR200, manufactured by Nippon Polyurethane Industry Co., Ltd.) in a reaction vessel while maintaining the temperature inside the reaction vessel at 65° C. After completion of the addition, the mixture was reacted at a temperature of 65° C. for 2 hours. The resulting reaction mixture was cooled to room temperature to obtain an isocyanate-terminated prepolymer P-1 having an isocyanate group content of 4.3%.
[0172] 57.0 parts by mass of isocyanate-terminated prepolymer P-1, 43.0 parts by mass of polyester polyol (trade name: P2010, manufactured by Kuraray Co., Ltd.), and 23 parts by mass of carbon black (trade name: MA230, manufactured by Mitsubishi Chemical Co., Ltd., number average particle size 30 nm) were dissolved in methyl ethyl ketone (MEK) to adjust the solid content to 27% by mass. Then, 0.1 parts by mass of modified dimethyl silicone oil (trade name: SH-28PA, manufactured by Toray Dow Corning Silicone Co., Ltd.) was added to prepare mixed solution 1. In a 450 mL glass bottle, 270 g of the mixed solution 1 and 200 g of glass beads with an average particle size of 0.8 mm were placed and dispersed for 12 hours using a paint shaker disperser. After dispersion, 15 parts by mass of urethane particles with an average particle size of 7.0 μm (product name: Dimic Beads UCN-5070D, manufactured by Dainichiseika Chemicals Co., Ltd.) were added. After that, the mixture was further dispersed for 15 minutes, and the glass beads were removed to obtain a surface layer coating solution 1.
[0173] [3-1. Preparation of charging roller 1] The conductive elastic roller 1 was oriented with its longitudinal direction in the vertical direction, and its upper end was gripped and dipped into the surface layer coating solution 1, and then pulled up. The dipping time for the dipping application was 9 seconds, and the roller pulling speed was adjusted so that the initial speed was 20 mm / sec and the final speed was 2 mm / sec, and the speed was changed linearly with respect to time between 20 mm / sec and 2 mm / sec. After coating, the coating was air-dried for 30 minutes at 23° C. Then, the coating was dried in a hot air circulation dryer at 80° C. for 1 hour and at 160° C. for 1 hour to form a dried coating film of the surface layer coating solution 1 on the elastic layer.
[0174] In addition, the cumulative amount of ultraviolet light with a wavelength of 254 nm is 9000 mJ / cm 2 The surface of the dry film was irradiated with ultraviolet light so that the outermost skin layer of the dry film was removed, and a surface layer was formed in which the conductive particles (conductive carbon black) in the dry film were exposed to the outer surface. A low-pressure mercury lamp (manufactured by Toshiba Lighting & Technology Corporation) was used as a light source of ultraviolet light. In this way, the charging roller 1 according to Example 1 was produced.
[0175] <4. Characterization> [4-1. Impedance measurement] The impedance measurement was carried out by the following measurement method. First, as a pretreatment, platinum was vapor-deposited onto the outer surface of the electrophotographic member, a charging roller, while rotating the charging roller, to prepare a measurement electrode (metal film). At this time, a masking tape was used to prepare an electrode with a width of 1.5 cm and uniform in the circumferential direction. By forming this electrode, it is possible to minimize the contribution of the contact area between the measurement electrode and the electrophotographic member due to the surface roughness of the electrophotographic member. Next, an aluminum sheet was tightly wrapped around the electrode to form a measurement sample.
[0176] An impedance measuring device (product name: Solartron 1260 96W, manufactured by Solartron) was then connected from the aluminum sheet to the measurement electrodes and to the substrate. The impedance was measured at a temperature of 23°C, a relative humidity of 50%, an oscillating voltage of 1 Vpp, and a frequency of 1.0 Hz to obtain the absolute value of the impedance.
[0177] The charging roller (length in the longitudinal direction: 230 mm) was divided into 5 equal regions in the longitudinal direction, and measurement electrodes were formed at one point in each region (a total of 5 points), and the above measurements were performed. The average value of these was taken as the impedance of the charging roller. The impedance of charging roller 1 is 4.3×10 5 It was Omega.
[0178] [4-2. Surface layer thickness measurement] The thickness of the surface layer was measured by observing a cross section of the surface layer at nine locations (three axial locations and three circumferential locations) with an optical microscope or an electron microscope, and the average value was taken as the "thickness" of the surface layer. The surface layer of the charging roller 1 had a thickness of 10 μm.
[0179] [4-3. Measurement of universal hardness of surface layer] The universal hardness at a position 1 μm deep from the surface of the surface layer was measured by a universal hardness tester. For the measurement, an ultra-microhardness tester (product name: FISCHERSCOPE HM-2000, manufactured by Helmut Fischer) was used. Specific measurement conditions are shown below. Measurement indenter: Vickers indenter (face angle 136, Young's modulus 1140, Poisson's ratio 0.07, indenter material: diamond) Measurement environment: Temperature 23℃, relative humidity 50% Maximum test load: 1.0mN Loading conditions: The load was applied in proportion to time at a rate that reached the maximum test load in 30 seconds. In this evaluation, the universal hardness was calculated by the following formula (1) using the load F when the indenter was pressed 1 μm deep from the surface of the surface layer and the contact area A between the indenter and the surface layer at that time. Calculation formula (1): Universal hardness (N / mm 2 )=F / A The universal hardness of the charging roller 1 is 3.2N / mm 2 It was.
[0180] <4-4. Measurement of volume resistivity (Ω cm) of surface layer> The volume resistivity of the surface layer was measured in the conductive mode using an atomic force microscope (AFM) (product name: Q-scope250:, Quesant). First, the surface layer of the charging roller was cut into a sheet with a width of 2 mm and a length of 2 mm using a manipulator, and platinum was vapor-deposited on one side of the surface layer. Next, a DC power source (product name: 6614C, Agilent) was connected to the platinum-deposited surface and 10 V was applied, and the free end of the cantilever was brought into contact with the other side of the surface layer, and a current image was obtained through the AFM body. This measurement was performed on 100 randomly selected points on the surface of the entire surface layer, and the "volume resistivity" was calculated from the average current value of the top 10 lowest current values and the average film thickness of the surface layer. The measurement conditions are as follows. Measurement mode: contact Cantilever: CSC17 Measurement range: 10μm x 10μm Scan rate: 4Hz Applied voltage: 10V The volume resistivity of the surface layer of the charging roller 1 is 6.8×10 10 It was Ωcm.
[0181] [4-5. Measurement of protrusions resulting from exposed areas of electronic conductive material on the outer surface of the surface layer] The method for measuring the number of protrusions resulting from the exposed portion of the electronic conductive agent on the surface of the surface layer is as follows. First, the elastic layer including the surface layer was cut out from the charging roller. Next, a scanning probe microscope (SPM) (product name: MFP-3D-Origin, manufactured by Asylum Technology) was used to perform tapping measurement with a cantilever on an area of 2.0 μm length × 2.0 μm width to obtain a height image. The obtained height image was subjected to image processing software (product name: Igor-Pro, manufactured by Hulinks Co., Ltd.) to extract protrusions of 5 nm or more in the height image by binarization processing, and the number of protrusions was calculated. Five SPM height images were obtained, and the arithmetic mean value of the calculated number of particles that were protruding was taken as the number of fine protrusions of the present disclosure. The measurement conditions are as follows. Measurement mode: AM-FM mode tapping measurement Cantilever: SI-DF3 Measurement range: 2μm x 2μm The number of minute protrusions caused by the exposure of the electronic conductive agent on the charging roller 1 was 210.
[0182] [4-6. Calculation of domain ratio in regions A and B in the elastic layer] An observation specimen for calculating the domain ratio of region A and region B in the elastic layer was prepared by the following method. A cross section parallel to the longitudinal direction of the charging roller and parallel to the outer surface was cut at 1 μm intervals using a microtome (product name: Leica EM FCS, manufactured by Leica Microsystems) at a cutting temperature of −100° C.
[0183] Of the slices prepared at 1 μm intervals in the thickness direction by the above method, the first slice (slice A) where the surface layer switches to the elastic layer, and a slice (slice B) shaved 5 μm further toward the elastic layer side than slice A were used. The surface on the elastic layer side of slice A is included in region A. Also, slice B is included in region B. Platinum was evaporated onto the first surface included in region A of the shaved slice A and the second surface included in region B of slice B.
[0184] Next, a scanning electron microscope (SEM) (product name: S-4800, manufactured by Hitachi High-Technologies Corporation) was used to take a 1000x image of the cross section. The obtained image was converted to 8-bit grayscale using image analysis software (product name: ImageProPlus, manufactured by Media Cybernetics Corporation) to obtain a monochrome image with 256 gradations. Next, the black and white of the image were inverted so that the second phase in the monochrome image became white, and a binarization threshold was set for the brightness distribution of the image based on the Otsu discriminant analysis algorithm to obtain a binarized image.
[0185] From the obtained binarized image, a square with one side of 100 μm was cut out, and the sum of the areas of the second phase in the observation regions (the first observation region in slice A, and the second observation region in slice B) was calculated. The sum of the areas of the second phase is the sum of the areas of the white regions in the binarized image. The area of the second phase calculated from slice A was designated AR12, and the area of the second phase calculated from slice B was designated AR22. AR11 and AR21 are the areas of the observation regions cut out above, and the areas were calculated from squares with one side of 100 μm.
[0186] Sections for observation were prepared at three locations, L1 / 4, L2 / 4, and L3 / 4, where L is the longitudinal length of the elastic layer, and the average values of the three locations were taken as the AR12 and AR22 values. The domain ratio AR12 / AR11 in the region A of the charging roller 1 was 0.52, and the domain ratio AR22 / AR21 in the region B was 0.24.
[0187] [4-7. Determination of matrix-domain structure (MD structure) in region B of elastic layer] The judgment was made using the binary image of section B obtained in 4-6 above. Using the same image processing software as in 4-6 above, and using the counting function of the software, the percentage K of the number of isolated domains that are not connected to each other was calculated out of the total number of domains that exist within a 50 μm square area and do not contact the border of the binary image. Sections for observation were prepared at three locations, L1 / 4, L2 / 4, and L3 / 4, where L is the longitudinal length of the elastic layer. If the arithmetic mean value of K at the three locations exceeded 80%, the MD structure was judged to be “present,” and if it was below 80%, it was judged to be “absent.” In the region B of the charging roller 1, the matrix-domain structure was "present" upon observation.
[0188] [4-8. Domain perimeter and envelope perimeter in region B of the elastic layer, and Measurement of the number of ins and the equivalent circle diameter D] Using the slice B prepared in 4-6 above, platinum was vapor-deposited on the cut flat surface. Next, a scanning electron microscope (SEM) (product name: S-4800, manufactured by Hitachi High-Technologies Corporation) was used to take a photograph at 5000 times magnification to obtain a cross-sectional image. The obtained image was converted to 8-bit grayscale using image analysis software (product name: ImageProPlus, manufactured by Media Cybernetics Corporation) to obtain a monochrome image with 256 gradations. Next, the black and white of the image were inverted so that the domains in the monochrome image became white, and a binarization threshold was set for the brightness distribution of the image based on the Otsu's discriminant analysis algorithm to obtain a binarized image.
[0189] A 15 μm square area was cut out from the binarized image, and the cross-sectional area, perimeter, and envelope perimeter were calculated using the counting function of the image processing software. For each domain, the calculated domain cross-sectional area S is d=(S / 2π) 0.5 The circle-equivalent diameter d of each domain was calculated by the above, and the number-average value of d was calculated as the circle-equivalent diameter D of the domain. Using the perimeter A and envelope perimeter B calculated for each domain observed in each observation region, A / B was calculated, and the percentage (number %) of domains in which A / B (requirement) was 1.00 to 1.10 was determined among all observed domains. In addition, the arithmetic mean diameter of all observed domains and the number of domains in the three observation regions were calculated.
[0190] The observation slices were prepared at three locations, L1 / 4, L2 / 4, and L3 / 4, where L is the longitudinal length of the elastic layer. The average values of the three locations were used as the proportion of domains where A / B satisfied the requirements and the average value of A / B, respectively. The proportion of domains in which A / B of charging roller 1 was 1.00 or more and 1.10 or less was 89%, and the arithmetic mean value of A / B was 1.06.
[0191] [4-9. Volume resistivity of regions A and B in the elastic layer, and volume resistivity of the matrix in region B] The volume resistivity of region A was calculated using slice A prepared in 4-6 above, and the volume resistivity of region B was calculated using slice B. Specifically, in an environment with a temperature of 23°C and a relative humidity of 50%, the surface on which platinum was deposited in step 4-6 was placed on a metal plate with the surface facing up, and a voltage of 50 V was applied between the metal plate and the platinum deposited surface, and the current value was measured. The slice thickness was 1 μm, and the volume resistivity was calculated from the thickness and the current value. When the longitudinal length of the elastic layer is L, the slice was prepared at three locations, L1 / 4, L2 / 4, and L3 / 4, and the average value of the three locations was taken as the volume resistivity of region A and region B. Region A Volume resistivity ρ A and ρ B From this, ρ B / ρ A was calculated.
[0192] Next, the volume resistivity of the matrix in region B was measured using a scanning probe microscope (SPM) (product name: Q-Scope250, manufactured by Quesant Instrument Corporation) operated in contact mode. First, slice B was obtained by the same method as in 4-6. Next, in an environment of 23°C and 50% relative humidity, the slice was placed on a metal plate, and among the parts that were in direct contact with the metal plate, the part corresponding to the matrix was selected and brought into contact with the cantilever of the SPM. Next, a voltage of 50 V was applied to the cantilever, and the current value was measured.
[0193] The surface shape of the measurement piece was observed with the SPM, and the thickness of the measurement point was calculated from the obtained height profile. The volume resistivity was calculated from the thickness and the current value, and was taken as the volume resistivity of the matrix. When the length of the elastic layer in the longitudinal direction is L, the elastic layer was prepared at three locations, L1 / 4, L2 / 4, and L3 / 4, and the average value of the three locations was taken as the volume resistivity of the matrix. The volume resistivity ratio ρ of region A and region B in the elastic layer of the charging roller 1 B / ρ A The volume resistivity of the matrix was 2.7×10 8 It was Ωcm.
[0194] [4-10. The ratio of the cross-sectional area of the conductive particles contained in the domain to the cross-sectional area of the domain S c / S calculation] Using the slice B with platinum deposition prepared in 4-6 above, a scanning electron microscope (SEM) (product name: S-4800, manufactured by Hitachi High-Technologies Corporation) was used to take an image at 20,000x magnification to obtain a cross-sectional image. Next, using image analysis software (product name: ImageProPlus, manufactured by Media Cybernetics Corporation), binarization was performed so that the carbon black in the domains could be distinguished. Furthermore, an observation area large enough to accommodate one domain was extracted from the obtained binarized image, and the cross-sectional area S of the domain and the cross-sectional area Sc of the carbon black as a conductive particle contained in the domain were calculated using a counting function, and S c The cross-sectional area ratio of the conductive particles in the domain was calculated using / S. Charging roller 1 S c / S was 26.7%.
[0195] <5. Evaluation as an electrostatic material> [5-1. Measurement of charge injected into toner] The charging roller 1 was evaluated for its ability to supply negative charge to contaminants (contaminants such as transfer residual toner and external additives) as follows. A laser printer (product name: HP LaserJet Pro M203dw, manufactured by HP) was prepared as an electrophotographic image forming apparatus. The motor of this laser printer was modified so that the process speed was 1.4 times faster than normal. Furthermore, an external power source was connected to apply voltage to the charging roller, and the printer was modified so that voltage was not directly applied to the charging roller from the main body. In addition, the cleaning blade of the charging roller and the developing container that contacts the photosensitive drum were removed from the process cartridge for this laser printer. The transfer roller of the main body of the laser printer was also removed.
[0196] The laser printer and process cartridge were left in a low-temperature, low-humidity environment (temperature 15°C, relative humidity 10%) for 48 hours. The process cartridge was then loaded into the laser printer. The following evaluations were then performed in the low-temperature, low-humidity environment. In a low-temperature, low-humidity environment, charge injection from the charging roller to the toner is unlikely to occur. By performing the following evaluations in such an environment, the charge injection capability of the charging roller can be evaluated more accurately.
[0197] First, the main body was stopped midway through an image forming process in which one solid black image was output under normal image output conditions, and a state was formed in which the entire circumference of the photosensitive drum was covered with a toner layer. Next, the process cartridge in which the entire circumference of the photosensitive drum was covered with a toner layer was removed from the main body. The charging roller of this process cartridge was removed, and charging roller 1 was installed as the charging roller, and this process cartridge was installed in the main body.
[0198] Then, a voltage at which the charging roller 1 does not discharge, specifically -500V, was applied from an external power source to the charging roller 1, and an image process was carried out to output one solid white image, during which the potential of the toner on the surface of the toner layer on the photosensitive drum was measured before and after passing through the nip between the charging roller and the photosensitive drum. The potential was measured using a surface potential meter probe (product name: MODEL555P-1, manufactured by Trek Japan) placed 2 mm away from the photosensitive drum surface.
[0199] The difference between the surface potential of the toner layer before passing through the nip portion and the surface potential of the toner layer after passing through the nip portion was measured as the amount of charge (V) injected into the toner by the charging roller. The charge amount injected into the toner by the charging roller 1 was −20.4V.
[0200] [5-2. Measurement of the amount of dirt (toner color density)] In order to evaluate the amount of dirt attached to the charging roller 1, the following evaluation was carried out. A laser printer (product name: HP LaserJet Pro M203dw, manufactured by HP) was prepared as an electrophotographic image forming apparatus. The motor of this laser printer was modified so that the process speed was 1.4 times faster than normal. Furthermore, an external power source was connected to apply voltage to the charging roller, and the printer was modified so that voltage was not applied directly to the charging roller from the main body. In addition, the cleaning blade of the charging roller was removed from the process cartridge for this laser printer. The evaluation environment was the same as that of 5-1 above.
[0201] First, 500 sheets of images were printed with horizontal lines of 2 dots wide and 100 dots apart in the direction perpendicular to the rotation direction of the photosensitive drum, and the charging roller 1 was removed from the process cartridge and the staining was evaluated by tape staining evaluation. The tape staining evaluation was performed as follows. After a polyester adhesive tape (product name: No. 31B, manufactured by Nitto Denko Corporation) was attached to the surface of the charging roller, the adhesive tape was peeled off together with the toner attached to the surface of the charging roller, and attached to a blank sheet of paper. This was performed for the entire image printing area on the surface of the charging roller, and the reflection density of the adhesive tape was measured for the entire image printing area using a Photovoltaic reflection densitometer (product name: TC-6DS / A, manufactured by Tokyo Denshoku Co., Ltd.) to obtain the maximum value. Next, the reflection density of a new polyester adhesive tape similarly attached to the blank sheet of paper was measured to obtain the minimum value, and the increase in reflection density was taken as the color density value. The smaller the color density value, the less dirt the charging roller has, and the better it is, so this was used as an index of the degree of dirt on the charging roller. The toner color concentration of charging roller 1 was 24%.
[0202] [5-3. Image evaluation] In the same main body and cartridge configuration as in 5-2 above, 20,000 images were output on A4 size paper in a low temperature and low humidity environment (temperature 15°C, relative humidity 10%), with the letter "E" in 4 points printed on the paper at a print rate of 1%. The output of the electrophotographic image was performed in a so-called intermittent mode, in which the rotation of the electrophotographic photosensitive member was stopped for 7 seconds after each output of the electrophotographic image. Compared to the case of continuously outputting electrophotographic images, the image output in the intermittent mode is a harsher evaluation condition for the charging roller because the number of times the charging roller rubs against the electrophotographic photosensitive member is greater.
[0203] Next, a halftone image (an image in which horizontal lines of 1 dot width and 2 dot intervals are drawn in the direction perpendicular to the rotation direction of the photosensitive drum) was output, and the resulting image was observed visually and with a magnifying glass and evaluated according to the following criteria. Rank A: There are absolutely no white spots even when viewed with a magnifying glass. Rank B: No white spots visible to the naked eye. Rank C: Slight white spots are visible to the naked eye. Rank D: White spots are visible across the entire area. When the charging roller 1 was used, no white spots were visually observed in the halftone image.
[0204] <Examples 2 to 22> Charging rollers 2 to 22 were produced in the same manner as in Example 1, except that the conditions for forming the elastic layer and the surface layer were changed to those shown in Table 8. Regarding the formulation of the rubber composition for forming the elastic layer in each elastic layer No. in Table 8, the CMB was produced with the blend shown in Table 4, the MRC with the blend shown in Table 5, and the rubber composition for forming the elastic layer with the blend shown in Table 6. In addition, the coating liquid for the surface layer was produced with the blend shown in Table 7. The parts in each table indicate parts by mass.
[0205] <Comparative Example 1> The CMB was changed to the composition shown in Table 4, the MRC to the composition shown in Table 5, and the conductive rubber composition to the composition shown in Table 6 to prepare a rubber composition 20 for forming an elastic layer. Thereafter, the rubber composition 20 for forming an elastic layer was coated on the same substrate as that used in Example 1. The detailed conditions are as follows. A crosshead extruder (manufactured by Mitsuba Manufacturing Co., Ltd.) was used to cover the conductive rubber composition 20 and prepare a crown-shaped unvulcanized rubber roller. A die with an inner diameter of 10.5 mm was attached to the tip of the crosshead. The molding temperatures of the cylinder, screw, and crosshead were each set to 100°C. The conveying speed of the substrate was adjusted to 60 mm / sec. At the die outlet, the conductive rubber flows out at the same speed as the core metal, so the flow speed of the conductive rubber composition 1' at the die outlet is 60 mm / sec, which is the same as the conveying speed of the substrate. The rotation speed of the screw was adjusted so that the outer diameter of the unvulcanized rubber roller was 10.3 mm at the longitudinal center with respect to the conveying speed of the substrate.
[0206] Next, the unvulcanized rubber roller was vulcanized by heating in an electric furnace at a temperature of 160° C. for 60 minutes, and both ends were cut off so that the length of the conductive rubber formed in the axial direction was 232 mm. Thereafter, the surface of the conductive rubber layer was polished by rotary polishing to obtain a conductive roller 20 having an elastic layer 20 with a diameter of 9.7 mm at the longitudinal center and a diameter of 9.65 mm at each position 90 mm away from the center to both ends. Finally, a surface layer was formed and a UV treatment was carried out in the same manner as in Example 1 to obtain a charging roller 23. The evaluation results are shown in Tables 8 to 10.
[0207] <Comparative Examples 2 and 3> Charging rollers 24 and 25 were produced in the same manner as in Comparative Example 1, except that the formulation of CMB was changed as shown in Table 4, the formulation of MRC was changed as shown in Table 5, and the formulation of the rubber composition for forming the elastic layer was changed as shown in Table 6. The evaluation results are shown in Tables 8 to 10.
[0208] [Table 4]
[0209] [Table 5]
[0210] [Table 6]
[0211] [Table 7]
[0212] [Table 8]
[0213] [Table 9] In the table, "Domain number" is the average number of domains in a 15 μm square observation region placed in region B. "A / B number %" indicates the percentage of domains with an A / B value of 1.00 to 1.10.
[0214] [Table 10]
[0215] The present disclosure relates to the following configurations. (Configuration 1) 1. An electrophotographic member comprising: a substrate having an electrically conductive surface; an elastic layer on the electrically conductive surface of the substrate; and a surface layer in contact with a surface of the elastic layer opposite a surface facing the substrate, the surface layer comprises an electronic conductive agent, A metal film is provided on the outer surface of the surface layer of the electrophotographic member, and an AC voltage having an amplitude of 1 V and a frequency of 1.0 Hz is applied between the conductive surface of the substrate and the metal film in an environment of a temperature of 23° C. and a relative humidity of 50%, and the impedance is 1.0×10 3 ~1.0×10 8 Ω, the elastic layer includes an insulating first phase including at least a cross-linked product of a first rubber, and a second phase including a cross-linked product of a second rubber different from the first rubber and conductive particles; The thickness of the elastic layer is 10 μm or more, the elastic layer has a matrix-domain structure in which domains made of the second phase are dispersed in a matrix made of the first phase in a region extending from an interface between the elastic layer and the surface layer to a depth direction of 5 μm or more into the elastic layer, A region having a thickness of 1 μm from the interface between the elastic layer and the surface layer to a position 1 μm deep into the elastic layer is defined as region A, A region having a thickness of 1 μm from the interface to a position 5 μm to 6 μm in a depth direction into the elastic layer is defined as region B, a first surface of the elastic layer in the region A is exposed, and a first observation region having a square shape with one side of 100 μm is placed at an arbitrary position on the first surface using a scanning electron microscope; the first observation region contains at least the second phase; The ratio (AR12 / AR11) of the sum AR12 of the area of the second phase in the first observation region to the area AR11 of the first observation region is greater than 0.40; and When the second surface of the elastic layer in the region B is exposed and a square second observation region with a side length of 100 μm is placed at an arbitrary position on the second surface using a scanning electron microscope, the matrix-domain structure is observed in the second observation region, and the ratio (AR22 / AR21) of the sum AR22 of the area of the second phase in the second observation region to the area AR21 of the second observation region is 0.40 or less. Electrophotographic member characterized in that: (Configuration 2) 2. The electrophotographic member according to embodiment 1, wherein AR12 / AR11 is 0.50 or greater. (Configuration 3) When an observation region of 15 μm square is placed at an arbitrary position on the second surface in the region B, and the perimeter of the domain is A and the envelope perimeter of the domain is B, 3. The electrophotographic member according to configuration 1 or 2, wherein the proportion of the domains in which the value of A / B is 1.00 to 1.10 is 80% by number or more. (Configuration 4) A ratio S of a cross-sectional area of the conductive particle to a cross-sectional area of the domain in the region B c 4. The electrophotographic member according to any one of configurations 1 to 3, wherein / S is 20.0 to 30.0%. (Configuration 5) The volume resistivity of the region A is ρ A , the volume resistivity of the region B is ρ B Then, ρ B / ρ A 5. The electrophotographic member according to any one of configurations 1 to 4, wherein the average molecular weight is ≧10.0. (Configuration 6) The volume resistivity ρm of the matrix in the region B is 1.0×10 8 Ωcm or more 1.0×10 17 6. The electrophotographic member according to any one of configurations 1 to 5, having a resistivity of Ωcm or less. (Configuration 7) the surface layer contains a binder resin and an electronic conductive agent dispersed in the binder resin, the outer surface of the surface layer has protrusions resulting from exposed portions of the electronic conductive agent; The surface layer has a universal hardness of 1.0 to 7.0 N / mm at a depth of 1 μm from the outer surface. 2 7. The electrophotographic member according to any one of Configurations 1 to 6, (Configuration 8) The first rubber includes at least one selected from the group consisting of isoprene rubber (IR), butadiene rubber (BR), styrene-butadiene rubber (SBR), and acrylonitrile butadiene rubber (NBR); The second rubber includes at least one selected from the group consisting of isoprene rubber (IR), butadiene rubber (BR), styrene-butadiene rubber (SBR), acrylonitrile butadiene rubber (NBR), and ethylene propylene diene rubber (EPDM); The electrophotographic member according to any one of Configurations 1 to 7. (Configuration 9) The absolute value of the difference in solubility parameter (SP value) between the first rubber and the second rubber is 0.4 to 5.7 (J / cm 3 ) 0.5 (Configuration 10) The electrophotographic member according to any one of Configurations 1 to 8, The combination of the first rubber and the second rubber is The first rubber is NBR and the second rubber is SBR; The first rubber is SBR and the second rubber is NBR; The first rubber is NBR and the second rubber is EPDM; The first rubber is SBR and the second rubber is EPDM; the first rubber is NBR and the second rubber is IR; or The first rubber is BR and the second rubber is NBR. 10. The electrophotographic member of claim 9. (Configuration 11) The electrophotographic member according to any one of configurations 1 to 10, wherein the electrophotographic member is a charging member. (Configuration 12) A process cartridge detachably mountable to an electrophotographic image forming apparatus, The process cartridge comprises the electrophotographic member according to any one of Configurations 1 to 11. (Configuration 13) 1. An electrophotographic image forming apparatus, comprising: The electrophotographic image forming apparatus comprises the electrophotographic member according to any one of Configurations 1 to 11. (Configuration 14) 14. The electrophotographic image forming apparatus according to Constitution 13, wherein the electrophotographic image forming apparatus comprises an electrophotographic photoreceptor and a charging member for charging the electrophotographic photoreceptor, the charging member being the electrophotographic member.< / epdm> < / sbr> < / nbr>
Claims
1. 1. An electrophotographic member comprising: a substrate having an electrically conductive surface; an elastic layer on the electrically conductive surface of the substrate; and a surface layer in contact with a surface of the elastic layer opposite a surface facing the substrate, the surface layer comprises an electronic conductive agent, A metal film is provided on the outer surface of the surface layer of the electrophotographic member, and an AC voltage having an amplitude of 1 V and a frequency of 1.0 Hz is applied between the conductive surface of the substrate and the metal film in an environment of a temperature of 23° C. and a relative humidity of 50%, and the impedance is 1.0×10 3 ~1.0 x 10 8 Ω, the elastic layer includes an insulating first phase including at least a cross-linked product of a first rubber, and a second phase including a cross-linked product of a second rubber different from the first rubber and conductive particles; The thickness of the elastic layer is 10 μm or more, the elastic layer has a matrix-domain structure in which domains made of the second phase are dispersed in a matrix made of the first phase in a region extending from an interface between the elastic layer and the surface layer to a depth direction of 5 μm or more into the elastic layer, A region having a thickness of 1 μm from the interface between the elastic layer and the surface layer to a position 1 μm deep into the elastic layer is defined as region A, A region having a thickness of 1 μm from the interface to a position of 5 μm to 6 μm in a depth direction into the elastic layer is defined as a region B. a first surface of the elastic layer in the region A is exposed, and a first observation region having a square shape with one side of 100 μm is placed at an arbitrary position on the first surface using a scanning electron microscope; the first observation region contains at least the second phase; The ratio (AR12 / AR11) of the sum AR12 of the areas of the second phases in the first observation region to the area AR11 of the first observation region is greater than 0.40; and when a second surface in the region B of the elastic layer is exposed and a square second observation region with a side length of 100 μm is placed at an arbitrary position on the second surface using a scanning electron microscope, the matrix-domain structure is observed in the second observation region, and a ratio (AR22 / AR21) of a sum AR22 of the area of the second phase in the second observation region to an area AR21 of the second observation region is 0.40 or less; Electrophotographic member characterized in that:
2. 2. The electrophotographic member of claim 1 wherein said AR12 / AR11 is 0.50 or greater.
3. When an observation region of 15 μm square is placed at an arbitrary position on the second surface in the region B, and the perimeter of the domain is A and the envelope perimeter of the domain is B, 2. The electrophotographic member according to claim 1, wherein the proportion of said domains having an A / B value of 1.00 to 1.10 is 80% or more by number.
4. A ratio S of a cross-sectional area of the conductive particle to a cross-sectional area of the domain in the region B c 2. The electrophotographic member of claim 1, wherein / S is from 20.0 to 30.0%.
5. The volume resistivity of the region A is ρ A , the volume resistivity of the region B is ρ B Then, ρ B / ρ A ≥ 10.
0.
6. The volume resistivity ρm of the matrix in the region B is 1.0×10 8 Ωcm or more 1.0×10 17 2. The electrophotographic member of claim 1 having a surface area of less than or equal to ohm-cm.
7. the surface layer contains a binder resin and an electronic conductive agent dispersed in the binder resin, the outer surface of the surface layer has protrusions resulting from exposed portions of the electronic conductive agent; The surface layer has a universal hardness of 1.0 to 7.0 N / mm at a depth of 1 μm from the outer surface. 2 2. The electrophotographic member of claim 1 wherein:
8. The first rubber includes at least one selected from the group consisting of isoprene rubber (IR), butadiene rubber (BR), styrene-butadiene rubber (SBR), and acrylonitrile butadiene rubber (NBR); The second rubber includes at least one selected from the group consisting of isoprene rubber (IR), butadiene rubber (BR), styrene-butadiene rubber (SBR), acrylonitrile butadiene rubber (NBR), and ethylene propylene diene rubber (EPDM); 2. The electrophotographic member of claim 1.
9. The absolute value of the difference in solubility parameter (SP value) between the first rubber and the second rubber is 0.4 to 5.7 (J / cm 3 ) 0.5 2. The electrophotographic member of claim 1 wherein
10. The combination of the first rubber and the second rubber is The first rubber is NBR and the second rubber is SBR; The first rubber is SBR and the second rubber is NBR; The first rubber is NBR and the second rubber is EPDM; The first rubber is SBR and the second rubber is EPDM; the first rubber is NBR and the second rubber is IR; or The first rubber is BR and the second rubber is NBR.
10. An electrophotographic member according to claim 9.
11. 2. The electrophotographic member of claim 1, wherein said electrophotographic member is a charging member.
12. A process cartridge detachably mountable to an electrophotographic image forming apparatus, The process cartridge comprises the electrophotographic member according to any one of claims 1 to 11.
13. 1. An electrophotographic image forming apparatus, comprising: The electrophotographic image forming apparatus comprises the electrophotographic member according to any one of claims 1 to 11.
14. 14. The electrophotographic image forming apparatus according to claim 13, further comprising an electrophotographic photoreceptor and a charging member for charging the electrophotographic photoreceptor, the charging member being the electrophotographic member.
Citation Information
Patent Citations
Conductive member, process cartridge, and electrophotographic image forming apparatus
JP2021067946A